Resin composition
A resin composition with specific polyphenylene ether backbones and an inorganic filler addresses brittleness and non-uniformity issues, achieving low dielectric loss tangent and good elongation for high-speed communication applications.
Patent Information
- Application Number
- CN202410784604.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-20
- Filing Date
- 2024-06-18
- Publication Date
- 2024-12-20
AI Technical Summary
Resins with a polyphenylene ether backbone exhibit brittleness and non-uniformity when compounded with inorganic fillers to achieve low dielectric loss tangent, which are detrimental for next-generation high-speed communication.
A resin composition combining two or more specific resins with different polyphenylene ether backbones, one with a higher molecular weight and glass transition temperature, and the other with a lower molecular weight, along with an inorganic filler, to achieve a cured product with low dielectric loss tangent, good elongation, and uniformity.
The composition produces a cured product with improved dielectric properties and mechanical flexibility, reducing transmission loss in high-frequency environments and ensuring uniformity.
Smart Images

Figure BDA0004898247770000051 
Figure BDA0004898247770000061 
Figure BDA0004898247770000071
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition. The present invention also relates to a resin sheet, a semiconductor chip package, a circuit board, and a semiconductor device. Background Art
[0002] For insulating materials such as sealing materials for semiconductor chip packages and interlayer insulating materials for circuit boards, the necessity of a low dielectric loss tangent has further increased for next-generation high-speed communication. Conventionally, a resin having a PPE (polyphenylene ether) backbone has been investigated as a chemical structure with a low dielectric loss tangent (for example, Patent Document 1).
[0003] Prior Art Documents Patent Documents Patent Document 1: Japanese Patent Application Laid-Open No. 2022-39594. Summary of the Invention
[0004] Technical Problem to be Solved by the Invention Although a resin having a PPE backbone is advantageous for a low dielectric loss tangent, problems are considered to be the brittleness (low elongation) derived from its rigid backbone and the non-uniformity (non-uniformity) caused by poor compatibility with other resins. It has been confirmed that the above problems are more significantly generated in the case of highly compounding an inorganic filler in order to achieve a low dielectric loss tangent.
[0005] An object of the present invention is to provide a resin composition that gives a cured product having a low dielectric loss tangent, a good elongation, and excellent uniformity.
[0006] Means for Solving the Technical Problem As a result of intensive studies by the present inventors, it has been found that the above problems can be solved by a resin composition having the following constitution in which two or more specific resins containing a low polyphenylene ether backbone (hereinafter, also referred to as "resin containing a low polyphenylene ether backbone") are combined, and thus the present invention has been completed.
[0007] That is, the present invention includes the following. [1] A resin composition, comprising: an inorganic filler, a resin X containing a low polyphenylene ether backbone having a weight average molecular weight Mw of MC, and a resin Y containing a low polyphenylene ether backbone having a weight average molecular weight Mw of MD, MC and MD satisfy the following Condition 1: <Condition 1> <1000000>MC>5MD>500 [2] A resin composition, comprising: an inorganic filler, A resin X containing an oligophenylene ether skeleton having a glass transition temperature of 25°C or less, and Resin Y containing an oligophenylene ether skeleton different from resin X. [3] The resin composition according to [1] or [2], wherein the total content of the resin X and the resin Y is 20% by mass or more and less than 70% by mass, based on 100% by mass of the resin component in the resin composition. [4] The resin composition according to any one of [1] to [3], wherein the content of the inorganic filler is 50% by mass or more when the non-volatile component in the resin composition is 100% by mass. [5] The resin composition according to any one of [1] to [4], wherein the resin X comprises one or more structural units selected from the group consisting of polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic acid structural units, and polysiloxane structural units. [6] The resin composition according to any one of [1] to [5], further comprising a thermosetting resin. [7] The resin composition according to any one of [1] to [6], which is used for semiconductor sealing. [8] The resin composition according to any one of [1] to [7], wherein the resin composition is used for an insulating layer of a circuit board. [9] A cured product of the resin composition according to any one of [1] to [8].
[10] A resin sheet comprising a support and a layer of the resin composition according to any one of [1] to [8] provided on the support.
[11] The resin sheet according to
[10] , wherein the support is a thermoplastic resin film or a metal foil.
[12] A semiconductor chip package comprising a sealing layer formed from a cured product of the resin composition according to any one of [1] to [7].
[13] A circuit board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to [6] and [8].
[14] A semiconductor device comprising the semiconductor chip package described in
[12] .
[15] A semiconductor device comprising the circuit substrate described in
[13] .
[0008] Effects of the Invention According to the present invention, a novel resin composition can be provided that produces a cured product having low dielectric loss tangent, good elongation, and excellent uniformity. DETAILED DESCRIPTION
[0009] <Explanation of terms> In this specification, the term "optionally having a substituent" with respect to a compound or group refers to both the case where hydrogen atoms of the compound or group are not substituted with a substituent and the case where some or all of the hydrogen atoms of the compound or group are substituted with a substituent.
[0010] In this specification, unless otherwise specified, the term "substituent" refers to a halogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an alkoxy group, a cycloalkyloxy group, an aryl group, an aryloxy group, an arylalkyl group, an arylalkoxy group, a monovalent heterocyclic group, an alkylidene group, an amino group, a silyl group, a carboxyl group, a sulfo group, a cyano group, a nitro group, a hydroxyl group, a mercapto group, and an oxo group. In this specification, a group consisting solely of carbon atoms and hydrogen atoms, such as an alkyl group, an alkenyl group, a cycloalkyl group, an aryl group, an arylalkyl group, and an alkylidene group, is also referred to as a hydrocarbon group.
[0011] Examples of the halogen atom that can be used as a substituent include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The alkyl group that can be used as a substituent may be either linear or branched. The number of carbon atoms in the alkyl group is preferably 1 to 12, more preferably 1 to 6, and even more preferably 1 to 3. The alkenyl group that can be used as a substituent may be either linear or branched. The number of carbon atoms in the alkenyl group is preferably 2 to 12, more preferably 2 to 6, and even more preferably 2 or 3. The cycloalkyl group that can be used as a substituent preferably has 3 to 12, more preferably 3 to 6 carbon atoms. The alkoxy group that can be used as a substituent may be either linear or branched. The number of carbon atoms in the alkoxy group is preferably 1 to 12, more preferably 1 to 6. The cycloalkoxy group that can be used as a substituent preferably has 3 to 12, more preferably 3 to 6 carbon atoms. The aryl group that can be used as a substituent is a group obtained by removing one hydrogen atom from an aromatic ring of an aromatic hydrocarbon. The number of carbon atoms of the aryl group which can be used as a substituent is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms of the aryloxy group which can be used as a substituent is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms of the arylalkyl group which can be used as a substituent is preferably 7 to 15, more preferably 7 to 11. The number of carbon atoms of the arylalkoxy group which can be used as a substituent is preferably 7 to 15, more preferably 7 to 11. The monovalent heterocyclic group which can be used as a substituent is a group obtained by removing one hydrogen atom from the heterocycle of a heterocyclic compound. The number of carbon atoms of the monovalent heterocyclic group is preferably 3 to 15, more preferably 3 to 9. The alkylidene group which can be used as a substituent is a group obtained by removing two hydrogen atoms from the same carbon atom of an alkane. The number of carbon atoms of the alkylidene group is preferably 1 to 12, more preferably 1 to 6, and even more preferably 1 to 3. The above-mentioned substituents may further have a substituent (hereinafter sometimes referred to as a "secondary substituent"). As the secondary substituent, unless otherwise specified, the same substituents as those described above can be used.
[0012] Hereinafter, embodiments and examples will be shown to describe the present invention in detail. However, the present invention is not limited to the following embodiments and examples, and any changes can be made without departing from the scope of the claims of the present invention and their equivalents.
[0013] [Discovery of the present invention] The present inventors have found that a resin composition that can achieve a cured product with a low dielectric loss tangent, good elongation, and excellent uniformity can be obtained by combining two or more specific resins containing a low polyphenylene ether backbone.
[0014] Specifically, it has been found that a resin composition that can achieve a cured product with a low dielectric loss tangent, good elongation, and excellent uniformity can be obtained by using a resin composition that combines a resin containing a low polyphenylene ether backbone with a relatively low molecular weight and a resin containing a low polyphenylene ether backbone with a molecular weight several times higher than that of this resin. In addition, if the present invention that combines two or more resins containing a low polyphenylene ether backbone is adopted, while enjoying the benefit of a lower dielectric loss tangent caused by a high content of inorganic filler, a cured product with good elongation and uniformity can be obtained. Thus, the present invention can advantageously reduce the transmission loss during operation in a high-frequency environment required for next-generation high-speed communication, and at the same time significantly play a role in realizing an insulating material with good elongation and uniformity.
[0015] [Resin composition] As described above, the resin composition of the present invention is characterized by containing a resin containing a low polyphenylene ether backbone with a molecular weight several times higher than that of a resin containing a low polyphenylene ether backbone with a relatively low molecular weight.
[0016] From the viewpoint of achieving a cured product with a low dielectric loss tangent, good elongation, and excellent uniformity, in a preferred embodiment, the resin composition of the present invention contains an inorganic filler, a resin X containing a low polyphenylene ether backbone with a weight-average molecular weight Mw of MC, and a resin Y containing a low polyphenylene ether backbone with a weight-average molecular weight Mw of MD, MC and MD satisfy the following condition 1: <Condition 1> <1000000> MC > 5MD > 500; Hereinafter, this embodiment will also be referred to as the "first embodiment". Here, resin Y corresponds to the aforementioned "resin containing a low polyphenylene ether backbone with a relatively low molecular weight", and resin X corresponds to the aforementioned "resin containing a low polyphenylene ether backbone with a molecular weight several times higher than that of this resin".
[0017] It should be noted that resins with higher molecular weights generally exhibit lower glass transition temperatures (Tg) than resins with lower molecular weights (resin Y). Resin X used in the present invention has a molecular weight more than five times higher than that of resin Y, and its glass transition temperature is generally below 25°C. Here, "the glass transition temperature of resin X is 25°C or lower" means that if resin X has only one glass transition temperature, the glass transition temperature is 25°C or lower. If resin X has multiple glass transition temperatures, at least one of the glass transition temperatures is 25°C or lower. In a preferred embodiment, the resin composition of the present invention comprises Inorganic filling materials, A resin X containing an oligophenylene ether skeleton having a glass transition temperature of 25°C or less, and A resin Y containing an oligophenylene ether skeleton different from the resin X; Hereinafter, this embodiment will also be referred to as the "Second Embodiment." Here, the glass transition temperature of resin Y is higher than 25°C, preferably higher than 60°C, more preferably higher than 80°C, and even more preferably higher than 100°C, higher than 120°C, or higher than 130°C. The upper limit of the glass transition temperature of resin Y is not particularly limited, but can generally be 350°C or lower, 340°C or lower, 320°C or lower, or 300°C or lower.
[0018] Hereinafter, each component will be described.
[0019] <Resin X containing an oligophenylene ether skeleton> Regardless of the first or second embodiment, the resin composition of the present invention includes a resin X containing an oligophenylene ether skeleton (also referred to as "resin X"). By using this resin X in combination with a resin Y containing an oligophenylene ether skeleton described later, a resin composition can be achieved that produces a cured product having a low dielectric loss tangent, good elongation, and excellent uniformity.
[0020] -Oligophenyl ether skeleton- The resin X preferably comprises an oligophenylene ether skeleton containing a plurality of phenylene ether units represented by the following formula (1).
[0021] [Chemical Formula 1] In formula (1), R each independently represents a halogen atom, an alkyl group optionally having a substituent, an alkoxy group optionally having a substituent, an aryl group optionally having a substituent, an amino group optionally having a substituent, a nitro group, or a carboxyl group, m represents an integer from 0 to 4.
[0022] The alkyl group and alkoxy group in R may be linear or branched, and the number of carbon atoms thereof is preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4 or 1 to 3. This number of carbon atoms does not include the number of carbon atoms in the substituent.
[0023] The number of carbon atoms of the aryl group in R is preferably from 6 to 14, more preferably from 6 to 10. This number of carbon atoms does not include the number of carbon atoms of the substituent.
[0024] The substituents that the monovalent group represented by R may have are as described above, and are preferably one or more selected from a halogen atom, an alkyl group, an alkoxy group, and an aryl group, more preferably one or more selected from a halogen atom, an alkyl group, and an aryl group, and further preferably one or more selected from a fluorine atom, an alkyl group having 1 to 6 carbon atoms, and an aryl group having 6 to 10 carbon atoms.
[0025] In formula (1), m represents an integer of 0 to 4, preferably an integer of 0 to 3, more preferably an integer of 1 to 3.
[0026] In combination with the resin Y containing an oligophenylene ether skeleton described later, from the viewpoint of producing a cured product with low dielectric loss tangent, good elongation and excellent uniformity, the oligophenylene ether skeleton is preferably an oligophenylene ether skeleton comprising a plurality of phenylene ether units selected from 2,6-disubstituted-1,4-phenylene ether units, 2,5-disubstituted-1,4-phenylene ether units and 2,3,6-trisubstituted-1,4-phenylene ether units, among which an oligophenylene ether skeleton comprising a plurality of 2,6-disubstituted-1,4-phenylene ether units is preferred; here, the substituents at the 2,6-position, the substituents at the 2,5-position and the substituents at the 2,3,6-position correspond to R in formula (1).
[0027] Specific examples of preferred oligophenylene ether skeletons include oligo(2,6-dialkyl-1,4-phenylene ether) skeletons, oligo(2-alkyl-6-aryl-1,4-phenylene ether) skeletons, oligo(2,6-diaryl-1,4-phenylene ether) skeletons, oligo(2,6-dihalogenated-1,4-phenylene ether) skeletons, and oligo(2,6-disubstituted-1,4-phenylene ether) skeletons; oligo(2,6-disubstituted-1,4-phenylene ether) skeletons formed from 2,6-disubstituted phenols and other phenolic compounds (e.g., The present invention relates to an oligophenylene ether skeleton comprising a plurality of 2,6-disubstituted-1,4-phenylene ether units, such as a skeleton formed by a copolymerization structure of 2,5-dialkylphenol, 2-alkyl-5-arylphenol, 2,5-diarylphenol, or a 2,3,6-trisubstituted phenol such as 2,3,6-trialkylphenol, 2,3,6-trihalogenatedphenol, or a coupling reaction product of 2,6-disubstituted phenol and a biphenol compound or a bisphenol compound.
[0028] In combination with the resin Y containing an oligophenylene ether skeleton described later, the resin X preferably contains a structure represented by the following formula (2) as the oligophenylene ether skeleton from the viewpoint of providing a cured product having a low dielectric loss tangent, good elongation, and excellent uniformity.
[0029] [Chemical Formula 2] In formula (2), R and m have the same meanings as above. L represents a divalent linking group, n1 and n2 each independently represent an integer of 1 to 100.
[0030] In formula (2), L represents a divalent linking group. Examples of the divalent linking group include a single bond, an alkylene group optionally having a substituent, an alkenylene group optionally having a substituent, an arylene group optionally having a substituent, an alkylarylene group optionally having a substituent, a heteroarylene group optionally having a substituent, -O-, -NH-, -NR- x -, -CO-, -CS-, -SO-, -SO2-, -C(=O)O-, -NHC(=O)-, -NC(=O)N-, -NHC(=O)O-, -C(=O)-, -S-, and a divalent group formed by combining a plurality of these groups. x It represents a hydrocarbon group having 1 to 12 carbon atoms.
[0031] Among them, from the viewpoint of being able to enjoy the effects of the present invention more, the divalent linking group represented by L is preferably a single bond, an alkylene group optionally having a substituent, an alkenylene group optionally having a substituent, an arylene group optionally having a substituent, -O-, -NR x -, -CO-, -CS-, -SO-, -SO2-, and a divalent group formed by combining multiple of these groups, preferably a single bond, an alkylene group optionally having a substituent, an arylene group optionally having a substituent, and a divalent group formed by combining multiple of these groups.
[0032] The substituents that the divalent group in L may have are as described above. From the viewpoint of being able to better enjoy the effects of the present invention, it is preferably one or more selected from halogen atoms and hydrocarbon groups, more preferably one or more selected from halogen atoms, alkyl groups and aryl groups, and even more preferably one or more selected from fluorine atoms, alkyl groups having 1 to 6 carbon atoms, and aryl groups having 6 to 10 carbon atoms.
[0033] The number of carbon atoms in the divalent linking group represented by L is preferably 60 or less, more preferably 48 or less, further preferably 36 or less, further preferably 24 or less.
[0034] Among them, in combination with the resin Y containing an oligophenylene ether skeleton described later, from the viewpoint of producing a cured product having a low dielectric loss tangent, good elongation and excellent uniformity, the divalent linking group represented by L is preferably an alkylene group having 1 to 6 carbon atoms, or a divalent group represented by the following formula (3).
[0035] [Chemical Formula 3] In formula (3), R 1 ~R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group, * indicates a key.
[0036] In formula (3), R 1 ~R 8 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group. 1 、R 2 、R 7 and R 8 It is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms. 3 and R 4 In the embodiment, one of the two is preferably a hydrogen atom and the other is preferably an alkyl group having 1 to 6 carbon atoms; 5 and R 6 In the above, one of them preferably represents a hydrogen atom and the other represents an alkyl group having 1 to 6 carbon atoms.
[0037] In formula (2), R and m are as described above for the phenylene ether unit of formula (1). From the viewpoint of being able to better enjoy the effects of the present invention, the phenylene ether unit constituting the oligophenylene ether skeleton represented by formula (2) is preferably a 2,6-disubstituted-1,4-phenylene ether unit, more preferably a 2,6-dialkyl-1,4-phenylene ether unit, a 2-methyl-6-aryl-1,4-phenylene ether unit, a 2,6-diaryl-1,4-phenylene ether unit, or a 2,6-dihalogenated-1,4-phenylene ether unit.
[0038] In combination with the resin Y containing an oligophenylene ether skeleton described later, the resin X preferably contains a structure represented by the following formula (2-1) as an oligophenylene ether skeleton from the viewpoint of producing a cured product with lower dielectric loss tangent, better elongation, and better uniformity.
[0039] [Chemical Formula 4] In formula (2-1), R, L, n1 and n2 have the same meanings as described above.
[0040] In formula (2-1), R, L, n1 and n2 have the same meanings as above, and preferred examples thereof are also as described above. Among them, from the viewpoint of being able to enjoy the effects of the present invention more, R each independently represents preferably a halogen atom, an alkyl group or an aryl group, more preferably a halogen atom, an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, and L is preferably a single bond, an alkylene group optionally having a substituent, an alkenylene group optionally having a substituent, an arylene group optionally having a substituent, -O-, -NR x -, -CO-, -CS-, -SO-, -SO2-, and a divalent group formed by combining a plurality of these groups, more preferably a single bond, an alkylene group optionally having a substituent, an arylene group optionally having a substituent, and a divalent group formed by combining a plurality of these groups, further preferably an alkylene group having 1 to 6 carbon atoms, or a divalent group represented by the above formula (3), n1 and n2 each independently represent an integer in the range of 1 to 100. In relation to the flexible skeleton described below, it is preferably an integer in a range such that the weight average molecular weight MC of the resin X satisfies the preferred conditions represented by Condition 1 (the condition will be described below), or at least one glass transition temperature of the resin X satisfies the preferred conditions (the condition will be described below).
[0041] -Soft skeleton- The resin X includes, in addition to the oligophenylene ether skeleton which is a rigid skeleton, a skeleton which is softer than the oligophenylene ether skeleton (also referred to simply as a "soft skeleton").
[0042] In combination with the resin Y containing an oligophenylene ether skeleton described later, from the viewpoint of achieving a cured product with lower dielectric loss tangent, better elongation, and better uniformity, the resin X preferably contains one or more structural units selected from the group consisting of polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic acid structural units, and polysiloxane structural units as a flexible skeleton.
[0043] Examples of the polyolefin structural unit include polyethylene structural units, polypropylene structural units, polybutadiene structural units, hydrogenated polybutadiene structural units, polyisoprene structural units, and hydrogenated polyisoprene structural units. Here, a "hydrogenated polybutadiene structural unit" refers to a structural unit in which some or all of the unsaturated bonds of a polybutadiene structural unit are hydrogenated; similarly, a "hydrogenated polyisoprene structural unit" refers to a structural unit in which some or all of the unsaturated bonds of a polyisoprene structural unit are hydrogenated.
[0044] For example, when resin X is produced using a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polyolefin structure) as described later, the polyolefin structural unit may be the remaining structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing a polyolefin structure. Commercially available polyol compounds containing a polyolefin structure may be used, and examples of such commercially available products include "G-1000," "G-2000," and "G-3000" (polybutadiene containing hydroxy groups at both ends) and "GI-1000," "GI-2000," and "GI-3000" (hydrogenated polybutadiene containing hydroxy groups at both ends) manufactured by Nippon Soda Co., Ltd.
[0045] Examples of the polycarbonate structural unit include aliphatic polycarbonates (polyethylene carbonate, polypropylene carbonate, polybutylene carbonate, polycyclohexyl carbonate, etc.) and aromatic polycarbonates (polybisphenol A carbonate, polybisphenol F carbonate, polybisphenol S carbonate, etc.).
[0046] For example, when the resin X is produced using a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polycarbonate structure) as described later, the polycarbonate structural unit may be the remaining structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing a polycarbonate structure. Commercially available polyol compounds containing a polycarbonate structure may be used, and examples of such commercially available products include "T6002" and "T6001" (polycarbonates containing hydroxyl groups at both ends) manufactured by Asahi Kasei Corporation, and "C-1090," "C-2015N," "C-2090," and "C-3090" (polycarbonates containing hydroxyl groups at both ends) manufactured by Kuraray Co., Ltd.
[0047] Examples of the polyether structural unit include a polyethylene glycol structural unit, a polypropylene glycol structural unit, a polytetramethylene glycol structural unit, and a polybutylene glycol structural unit.
[0048] For example, when the resin X is produced using a polyol compound having a flexible skeleton (a polyol compound containing a polyether structure in this embodiment) as described later, the polyether structural unit may be a structural unit remaining after removing two or more hydroxyl groups from the polyol compound containing a polyether structure. As the polyol compound containing a polyether structure, commercially available products can be used. Examples of such commercial products include "PLONON #102", "PLONON #104", "PLONON #201", "PLONON #202B", "PLONON #204", "PLONON #208", "UNILUBE 70DP-600B", and "UNILUBE 70DP-950B" (polyethylene glycol-polypropylene glycol copolymers) manufactured by NOF Corporation; and "Pluronic (registered trademark) L-23", "Pluronic L-31", "Pluronic L-44", "Pluronic L-61", "ADEKA Pluronic L-62", "Pluronic L-64", "Pluronic L-71", "Pluronic L-72", "Pluronic L-101", "Pluronic L-121", "Pluronic P-84", "Pluronic P-85", and "Pluronic L-126" manufactured by ADEKA Corporation. P-103", "Pluronic F-68", "Pluronic F-88", "Pluronic F-108", "Pluronic 25R-1", "Pluronic 25R-2", "Pluronic 17R-2", "Pluronic 17R-3", "Pluronic 17R-4" (polyethylene glycol-polypropylene glycol copolymer).
[0049] Examples of the polyester structural unit include a polyethylene terephthalate structural unit, a polybutylene terephthalate structural unit, a polyethylene naphthalate structural unit, a polybutylene naphthalate structural unit, and a polytrimethylene terephthalate structural unit.
[0050] For example, when the resin X is produced using a polyol compound having a flexible skeleton (a polyol compound containing a polyester structure in this embodiment) as described later, the polyester structural unit may be the remaining structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing a polyester structure. Commercially available polyol compounds containing a polyester structure may be used, and examples of such commercially available products include VYLON (registered trademark) manufactured by Toyobo Co., Ltd., POLYESTER (registered trademark) manufactured by Nippon Synthetic Chemical Industry Co., Ltd., and SLACK (registered trademark) manufactured by Resonac Co., Ltd.
[0051] The poly(meth)acrylic acid structural unit refers to a structural unit containing a plurality of "at least one of an acrylic acid structure and a methacrylic acid structure". For example, when a polyol compound having a flexible skeleton (a polyol compound containing a poly(meth)acrylic acid structure in this embodiment) is used to produce resin X as described later, the poly(meth)acrylic acid structural unit may be a structural unit remaining after removing two or more hydroxyl groups from the polyol compound containing a poly(meth)acrylic acid structure. Commercially available polyol compounds containing a poly(meth)acrylic acid structure may be used. Examples of such commercially available products include Teisan Resin "SG-600TEA" and "SG-790" (hydroxyl-containing acrylate copolymer resins) manufactured by Nagase ChemteX Co., Ltd. and "W-197C" (hydroxyl-containing acrylate copolymer resin) manufactured by Negami Industries Co., Ltd.
[0052] Examples of the polysiloxane structural unit include a dialkyl polysiloxane structural unit, a diaryl polysiloxane structural unit, a monoalkyl monoaryl polysiloxane structural unit, and a monoalkyl polysiloxane structural unit.
[0053] For example, when resin X is produced using a polyol compound having a flexible skeleton (in this embodiment, a polyol compound containing a polysiloxane structure) as described later, the polysiloxane structural unit may be the remaining structural unit obtained by removing two or more hydroxyl groups from the polyol compound containing a polysiloxane structure. Commercially available polyol compounds containing a polysiloxane structure may be used, and examples of such commercially available products include "X-21-5841" and "KF-9701" (both terminal hydroxyl polysiloxanes) manufactured by Shin-Etsu Chemical Co., Ltd.
[0054] As described above, resin X comprises an oligophenylene ether skeleton and a flexible skeleton. The mass ratio of the oligophenylene ether skeleton to the flexible skeleton in resin X (flexible skeleton / oligophenylene ether skeleton) is not particularly limited as long as the weight average molecular weight MC of resin X satisfies the preferred conditions represented by condition 1 (the conditions will be described later) or the glass transition temperature of resin X satisfies the preferred conditions (the conditions will be described later). The mass ratio (flexible skeleton / oligophenylene ether skeleton) is preferably 0.2 or more, more preferably 0.4 or more, and further preferably 0.5 or more, 0.6 or more, or 0.7 or more. The mass ratio condition can be, for example, 3 or less, 2.5 or less, 2 or less, etc.
[0055] In the first embodiment, the weight average molecular weight MC of resin X satisfies condition 1 in relation to the weight average molecular weight MD of resin Y containing an oligophenylene ether skeleton described later (i.e., it is more than 5 times higher than the weight average molecular weight MD of resin Y and less than 1,000,000). In the above embodiment, the weight average molecular weight MC of resin X is not particularly limited as long as it satisfies condition 1. However, in combination with resin Y containing an oligophenylene ether skeleton described later, from the perspective of achieving a cured product with lower dielectric loss tangent, better elongation, and better uniformity, the weight average molecular weight MC of resin X is preferably more than 10 times (MC>10MD), more preferably more than 15 times (MC>15MD), and even more preferably more than 20 times, more than 25 times, more than 30 times, more than 35 times, or more than 40 times (MC>20MD, MC>25MD, MC>30MD, MC>35MD, or MC>40MD) higher than the weight average molecular weight MD of resin Y.
[0056] In the first embodiment, from the viewpoint of achieving the effects of the present invention, the upper limit of the weight average molecular weight MC of the resin X is less than 1,000,000, preferably less than 800,000, more preferably less than 600,000, and further preferably less than 500,000.
[0057] In the present invention, the weight average molecular weights MC and MD of the resins X and Y can be respectively based on polystyrene-equivalent values measured by gel permeation chromatography (GPC).
[0058] In the second embodiment, the resin X has a glass transition temperature of 25°C or less. If the resin X has only one glass transition temperature, the glass transition temperature is 25°C or less. If the resin X has multiple glass transition temperatures, at least one glass transition temperature is 25°C or less. When the resin X has multiple glass transition temperatures, there is no particular limitation on the other glass transition temperatures as long as the resin X has a glass transition temperature of 25°C or less. In combination with the resin Y containing an oligophenylene ether skeleton described later, from the perspective of achieving a cured product with lower dielectric loss tangent, better elongation, and better uniformity, the glass transition temperature of the resin X below 25°C is preferably 10°C or less, more preferably 5°C or less, and even more preferably 0°C or less.
[0059] In the present invention, the glass transition temperature of the resin X (and the resin Y) is based on a value measured by DSC (differential scanning calorimetry) at a temperature increase rate of 5° C. / min.
[0060] In combination with the oligophenylene ether skeleton-containing resin Y described later, from the perspective of producing a cured product with lower dielectric loss tangent, better elongation, and superior uniformity, the resin X preferably has a weight average molecular weight MC that satisfies condition 1 and exhibits a glass transition temperature of 25°C or lower. The preferred ranges of the weight average molecular weight MC and the glass transition temperature are as described in connection with the first and second embodiments, respectively.
[0061] -Synthesis of Resin X- The synthesis process of the resin X is not particularly limited as long as it can realize the above-mentioned structure including the oligophenylene ether skeleton and the flexible skeleton.
[0062] An example of the synthesis procedure of resin X is shown below.
[0063] In one embodiment, the resin X is obtained by making (x1) a polyol compound having a flexible skeleton, (x2) polyisocyanate compounds, (x3) a compound containing an acid anhydride group, and (x4) a polyol compound containing an oligophenylene ether skeleton Obtained by reaction.
[0064] In this reaction, the flexible backbone of component (x1) is bonded to the oligophenylene ether backbone of component (x4) via the imide structure (preferably a cyclic imide structure) formed by the reaction of component (x2) and component (x3). Therefore, in one embodiment, resin X contains an imide structure (preferably a cyclic imide structure).
[0065] Regarding component (x1), preferred examples of the flexible skeleton are as described above. As component (x1), any polyol compound containing a flexible skeleton can be used depending on the structure (i.e., flexible skeleton) of the target resin X. Examples of commercially available products are as described above with respect to the flexible skeleton. Component (x1) can be used alone or in combination of two or more, depending on the type of flexible skeleton contained in resin X.
[0066] The polyisocyanate compound as component (x2) is not particularly limited in type as long as it can react with a hydroxyl group and react with component (x3) to form an imide structure. Examples of the polyisocyanate compound include aliphatic diisocyanate compounds such as butane diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; alicyclic diisocyanate compounds such as norbornane diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate; phenylene diisocyanate (p-phenylene diisocyanate, m-phenylene diisocyanate), xylene diisocyanate (p-xylene diisocyanate, m-xylene diisocyanate), and toluene diisocyanate (toluene-2-ylene diisocyanate). Aromatic diisocyanate compounds such as 1,3-bis(α,α-dimethylisocyanatomethyl)benzene, tetramethylxylylene diisocyanate, diphenyl ether-4,4'-diisocyanate, and naphthalene diisocyanate; polymethylene polyphenyl polyisocyanate; and isocyanurate-modified products thereof, biuret-modified products thereof, and allophanate-modified products thereof. Component (x2) may be used alone or in combination of two or more.
[0067] The type of the acid anhydride group-containing compound as component (x3) is not particularly limited as long as it can react with component (x2) to form an imide structure (preferably a cyclic imide structure). As the acid anhydride group-containing compound, tetracarboxylic dianhydride can be preferably used, and examples thereof include pyromellitic dianhydride, benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic anhydride, p-phenylene trimellitic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, cyclobutane tetracarboxylic dianhydride, cyclopentane tetracarboxylic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, and 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-C]furan-1,3-dione. The component (x3) may be used alone or in combination of two or more.
[0068] Regarding component (x4), preferred examples of oligophenylene ether skeletons are as described above. As component (x4), any polyol compound containing an oligophenylene ether skeleton can be used, depending on the structure of the target resin X (i.e., the oligophenylene ether skeleton). For example, as a polyol compound containing an oligophenylene ether skeleton represented by formula (2-1), "NORYL SA90" manufactured by SABIC Innovative Plastics can be cited. Component (x4) can be used alone or in combination of two or more, depending on the type of oligophenylene ether skeleton contained in resin X.
[0069] The synthesis reaction of the resin X using these components (x1) to (x4) can be carried out under the conditions generally used in the imidization reaction using a polyol compound, an isocyanate compound, and an acid anhydride group-containing compound. The reaction raw materials containing components (x1) to (x4) can be reacted together, or the components (x1) to (x4) can be reacted sequentially. When the reaction raw materials containing components (x1) to (x4) are reacted together, the reaction temperature can be set to, for example, a range of 100 to 160°C, and the reaction time can be set to, for example, a range of 4 to 10 hours. In addition, when components (x1) to (x4) are reacted sequentially, components (x1) and (x2) can be reacted at, for example, a range of 50 to 100°C for 0.5 to 4 hours, and then components (x3) and (x4) can be added and reacted at, for example, 120 to 160°C for 3 to 6 hours.
[0070] A catalyst may be used in the reaction of components (x1) to (x4). Examples of the catalyst include tertiary amines such as tetramethylbutanediamine, benzyldimethylamine, triethanolamine, triethylamine, N,N'-dimethylpiperidine, α-methylbenzyldimethylamine, N-methylmorpholine, and triethylenediamine; and organometallic catalysts such as dibutyltin laurate, dimethyltin dichloride, cobalt naphthenate, and zinc naphthenate.
[0071] In the above reaction, by changing the degree of reaction between component (x1) and component (x2) and the quantitative ratio of component (x1) to component (x4), the molecular weight of resin X and the proportion of the soft skeleton in resin X, and thus the glass transition temperature of resin X, can be adjusted.
[0072] <Resin Y containing an oligophenylene ether skeleton> Regardless of the first or second embodiment, the resin composition of the present invention includes a resin Y containing an oligophenylene ether skeleton (also referred to as "resin Y"). By using this resin Y in combination with the above-mentioned resin X containing an oligophenylene ether skeleton, a resin composition can be achieved that produces a cured product having a low dielectric loss tangent, good elongation, and excellent uniformity.
[0073] Resin Y contains an oligophenylene ether skeleton similarly to Resin X. Preferred examples of the oligophenylene ether skeleton contained in Resin Y are as described with respect to Resin X.
[0074] That is, the resin Y preferably contains an oligophenylene ether skeleton containing a plurality of phenylene ether units represented by the above formula (1), and preferably contains a plurality of 2,6-disubstituted-1,4-phenylene ether units. Preferred specific examples of the oligophenylene ether skeleton contained in the resin Y include oligo(2,6-dialkyl-1,4-phenylene ether) skeletons, oligo(2-alkyl-6-aryl-1,4-phenylene ether) skeletons, oligo(2,6-diaryl-1,4-phenylene ether) skeletons, oligo(2,6-dihalogenated-1,4-phenylene ether) skeletons, and oligo(2,6-disubstituted-1,4-phenylene ether) skeletons. The present invention relates to a skeleton formed by a copolymerization structure of a 2,5-disubstituted phenol (for example, 2,5-dialkylphenol, 2-alkyl-5-arylphenol, 2,5-diarylphenol or 2,3,6-trisubstituted phenol such as 2,3,6-trialkylphenol, 2,3,6-trihalogenatedphenol), an oligophenyl ether skeleton containing multiple 2,6-disubstituted-1,4-phenyl ether units such as a coupling reaction product of a 2,6-disubstituted phenol and a biphenol or bisphenol compound.
[0075] In combination with the aforementioned resin X, from the perspective of producing a cured product with low dielectric loss tangent, good elongation, and excellent uniformity, resin Y preferably includes a structure represented by the above formula (2) as an oligophenylene ether skeleton. In such a case, R, m, L, n1, and n2 in formula (2) are as described above, including preferred examples thereof. In addition, from the perspective of being able to better enjoy the effects of the present invention, the ends of resin Y are each independently preferably a hydroxyl group, a (meth)acryloyloxy group, an alkenyl group, or an alkoxysilyl group.
[0076] In combination with the above-mentioned resin X, the resin Y is preferably a compound represented by the following formula (4) from the viewpoint of providing a cured product having a low dielectric loss tangent, good elongation and excellent uniformity.
[0077] [Chemical Formula 5] In formula (4), R, m, L, n1 and n2 have the same meanings as above; X each independently represents (i) a hydrogen atom, (ii) a (meth)acryloyl group, (iii) a monovalent group represented by the following formula (X-1), or (iv) a monovalent hydrocarbon group substituted with a (meth)acryloyloxy group or an alkoxysilyl group.
[0078] [Chemical Formula 6] In formula (X-1), R means the same as above; A represents an alkylene group optionally having a substituent; Y represents an alkenyl group or a (meth)acryloyloxy group; m1 represents an integer from 0 to 4.
[0079] In the formula (4), R and m, including preferred examples thereof, are as described above with respect to the phenylene ether unit of the formula (1).
[0080] In formula (4), L, including preferred examples thereof, is as described above with respect to the oligophenylene ether skeleton of formula (2).
[0081] In formula (4), n1 and n2 each independently represent an integer in the range of 1 to 100, preferably an integer in a range such that the weight average molecular weight MD of the resin Y satisfies the preferred conditions represented by Condition 1.
[0082] In formula (4), X each independently represents (i) a hydrogen atom, (ii) a (meth)acryloyl group, (iii) a monovalent group represented by formula (X-1), or (iv) a hydrocarbon group substituted with a (meth)acryloyloxy group or an alkoxysilyl group. Here, the term "(meth)acryloyl group" encompasses both methacryloyl and acryloyl groups, and the term "(meth)acryloyloxy group" encompasses both methacryloyl and acryloyl groups.
[0083] Hereinafter, the case where X represents a monovalent group represented by the above formula (X-1), that is, the above embodiment (iii) will be described.
[0084] In the formula (X-1), R, including preferred examples thereof, is as described above with respect to the phenylene ether unit of the formula (1).
[0085] In formula (X-1), A represents an alkylene group optionally having a substituent. The alkylene group in A may be either linear or branched, and the number of carbon atoms thereof is preferably 1 to 10, more preferably 1 to 6, and even more preferably 1 to 3. The substituents that the alkylene group may have are as described above. From the perspective of being able to better enjoy the effects of the present invention, it is preferably one or more selected from halogen atoms and hydrocarbon groups, more preferably one or more selected from halogen atoms, alkyl groups, and aryl groups, and even more preferably one or more selected from fluorine atoms, alkyl groups having 1 to 6 carbon atoms, and aryl groups having 6 to 10 carbon atoms.
[0086] In formula (X-1), Y represents an alkenyl group or a (meth)acryloyloxy group. The alkenyl group represented by Y may be linear or branched, and preferably has 2 to 10 carbon atoms, more preferably 2 to 6 carbon atoms, and even more preferably 2 or 3 carbon atoms. In combination with resin X, the alkenyl group represented by Y is preferably a vinyl group or an allyl group, from the viewpoint of achieving a greater effect of the present invention.
[0087] In formula (X-1), m1 represents an integer of 0 to 4, preferably 0 to 2, more preferably 0 or 1, further preferably 0.
[0088] Hereinafter, the case where X represents a hydrocarbon group substituted with a (meth)acryloyloxy group or an alkoxysilyl group, that is, the above-mentioned embodiment (iv) will be described.
[0089] Regardless of whether X represents a hydrocarbon group substituted with a (meth)acryloyloxy group or a hydrocarbon group substituted with an alkoxysilyl group, the hydrocarbon group in X is a hydrocarbon group having only one or more (preferably 1 to 50, more preferably 1 to 20) carbon atoms as backbone atoms and hydrogen atoms as non-backbone atoms. The hydrocarbon group may be a saturated hydrocarbon group or an unsaturated hydrocarbon group. The hydrocarbon group may or may not have an aromatic structure. Examples of the hydrocarbon group include alkyl groups, alkenyl groups, aryl groups, arylalkyl groups (aralkyl groups), alkylaryl groups, alkylaralkyl groups, alkenylaryl groups, alkenylaralkyl groups, alkenylalkylaryl groups, and alkenylalkylaralkyl groups. Here, the number of carbon atoms of the alkyl group is preferably 1 to 14, more preferably 1 to 6; the number of carbon atoms of the alkenyl group is preferably 2 to 14, more preferably 2 to 6; the number of carbon atoms of the aryl group is preferably 6 to 14, more preferably 6 to 10; the number of carbon atoms of the aralkyl group and the arylalkyl group is preferably 7 to 15, more preferably 7 to 11; the number of carbon atoms of the alkylaralkyl group is preferably 8 to 16, more preferably 8 to 12; the number of carbon atoms of the alkenylaryl group is preferably 8 to 15, more preferably 8 to 11; the number of carbon atoms of the alkenylaralkyl group and the alkenylalkylaryl group is preferably 9 to 16, more preferably 9 to 12; and the number of carbon atoms of the alkenylalkylaralkyl group is preferably 10 to 17, more preferably 10 to 13. One or more hydrogen atoms of these hydrocarbon groups may be substituted with a (meth)acryloyloxy group or an alkoxysilyl group.
[0090] When X represents a hydrocarbon group substituted with an alkoxysilyl group, examples of the alkoxysilyl group include trialkoxysilyl, dialkoxymonoalkylsilyl, and monoalkoxydialkylsilyl. The number of carbon atoms in the alkoxysilyl group is preferably 1 to 6, more preferably 1 to 4, and further preferably 1 or 2, and the number of carbon atoms in the alkyl group (including the alkyl group) in the alkoxysilyl group is preferably 1 to 14, more preferably 1 to 10, and further preferably 1 to 6.
[0091] In the first embodiment, the weight average molecular weight MD of resin Y satisfies condition 1 in relation to the weight average molecular weight MC of the aforementioned resin X, i.e., it is greater than 100 and less than 1 / 5 of the weight average molecular weight MC of resin X. In the above embodiment, the weight average molecular weight MD of resin Y is not particularly limited as long as it satisfies condition 1. However, in combination with the aforementioned resin X, from the perspective of achieving a cured product with lower dielectric loss tangent, better elongation, and better uniformity, the lower limit of the weight average molecular weight MD of resin Y is greater than 100, preferably greater than 500, more preferably greater than 1000, and even more preferably greater than 1500 or greater than 2000. The preferred range of the upper limit of the weight average molecular weight MD of resin Y is as described above in relation to the weight average molecular weight MC of resin X.
[0092] In the second embodiment, the glass transition temperature of the resin Y is higher than 25° C., and the preferred range thereof is as described above.
[0093] In combination with resin X, resin Y preferably has a weight average molecular weight MD that satisfies condition 1 and exhibits a glass transition temperature higher than 25°C, from the viewpoint of producing a cured product with lower dielectric loss tangent, better elongation, and superior uniformity. The preferred ranges of the weight average molecular weight MD and the glass transition temperature are as described in connection with the first and second embodiments, respectively.
[0094] Resin Y can be a commercially available product, for example, "NORYL SA9000" manufactured by SABIC Innovative Plastics (wherein R is a methyl group, m is 2, L is a C3 alkylene group, X is a methacryloyl group, n1 and n2 are values such that the weight average molecular weight becomes about 3900; and contains an oligo(2,6-dialkyl-1,4-phenylene ether) skeleton), "NORYL SA90" (wherein R is a methyl group, m is 2, L is a C3 alkylene group, X is a hydrogen atom, n1 and n2 are values such that the weight average molecular weight becomes approximately 4400, and it contains an oligo(2,6-dialkyl-1,4-phenylene ether) skeleton), "OPE-2St" manufactured by Mitsubishi Gas Chemical Co., Ltd. (wherein R is a methyl group, m is 2, L is a divalent group represented by formula (3), X is a group represented by formula (X-1) [m1 is 0, A is a C1 alkylene group, and Y is a C2 alkenyl group], n1 and n2 is a value such that the weight average molecular weight becomes approximately 3000, and contains an oligo(2,6-dialkyl-1,4-phenylene ether) skeleton), "X-12-1288C" and "X-12-1288D" manufactured by Shin-Etsu Chemical Co., Ltd. (in formula (4), R is a methyl group, m is 2, X is a hydrocarbon group substituted with a methacryloyloxy group or a trialkoxysilyl group, n1 and n2 are values such that the weight average molecular weight becomes approximately 3500 to 3600, and contains an oligo(2,6-dialkyl-1,4-phenylene ether) skeleton).
[0095] From the viewpoint of bringing dielectric loss tangent low, presenting good elongation, the cured product of excellent uniformity, when the resin component in resin combination is set to 100 mass %, the total content of resin X and resin Y in resin combination is preferably more than 20 mass %, more preferably more than 25 mass %, further more preferably more than 30 mass %, more than 32 mass %, more than 34 mass % or more than 35 mass %.According to same viewpoint, the upper limit of this total content is preferably less than 70 mass %, more preferably less than 65 mass %, further more preferably less than 60 mass %, less than 58 mass %, less than 56 mass % or less than 55 mass %.Therefore, in one embodiment, when the resin component in resin combination is set to 100 mass %, the total content of resin X and resin Y is more than 20 mass % and less than 70 mass %.
[0096] In the present invention, the "resin component" referred to in the resin composition refers to the components other than the inorganic filler described below among the non-volatile components constituting the resin composition.
[0097] From the viewpoint of bringing dielectric loss tangent lower, presenting better elongation, uniformity is more excellent solidified material, the mass ratio of resin X relative to resin Y (resin X / resin Y) is preferably more than 0.3 or more than 0.5, more preferably more than 0.6, more than 0.8 or more than 1, further more preferably higher than 1, more than 1.2, more than 1.4, more than 1.5, more than 1.6, more than 1.8 or more than 2, further more preferably more than 2.2, more than 2.4 or more than 2.5. Especially if the mass ratio of resin X / resin Y is higher than 1, dielectric loss tangent, elongation, uniformity are all excellent solidified material, so preferably. According to the same viewpoint, the upper limit of this mass ratio is preferably less than 20, more preferably less than 15, further more preferably less than 10, less than 9.5 or less than 9.
[0098] The content of resin X in the resin composition is not particularly limited as long as it satisfies the preferred ranges of the above-mentioned total content and mass ratio in relation to the content of resin Y. When the resin component in the resin composition is set to 100 mass%, it is preferably 5 mass% or more, more preferably 10 mass% or more, further more preferably 15 mass% or more, further more preferably 20 mass% or more, 22 mass% or more, 24 mass% or more, or 25 mass% or more. The upper limit is preferably 66 mass% or less, more preferably 60 mass% or less, further more preferably 55 mass% or less, 50 mass% or less, 48 mass% or less, 46 mass% or less, or 45 mass% or less.
[0099] <Inorganic fillers> Regardless of the first embodiment or the second embodiment, the resin composition of the present invention contains an inorganic filler. By containing an inorganic filler, the dielectric loss tangent can be reduced.
[0100] As the inorganic filler, for example, silica, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum silicate, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate etc. can be enumerated. Among them, silica is particularly preferred. As silica, amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica etc. can be enumerated. In addition, as silica, spherical silica is preferably used. One inorganic filler can be used alone or in combination of two or more.
[0101] Examples of commercially available inorganic fillers include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemicals Co., Ltd., "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Yaduma Co., Ltd., "UFP-30", "DAW-03", and "FB-105FD" manufactured by DENKA Corporation, "SILFIL NSS-3N", "SILFIL NSS-4N", and "SILFIL NSS-5N" manufactured by Tokuyama Co., Ltd., and "CellSpheres" and "MGH-005" manufactured by Pacific Cement Co., Ltd.
[0102] The average particle size of the inorganic filler is not particularly limited, and is preferably less than 10 μm, more preferably less than 5 μm, and further preferably less than 3 μm, less than 2 μm, less than 1 μm or less than 0.7 μm. The lower limit of the average particle size is not particularly limited, and is preferably more than 0.01 μm, more preferably more than 0.05 μm, and further preferably more than 0.07 μm, more than 0.1 μm or more than 0.2 μm. The average particle size of the inorganic filler can be measured by a laser diffraction scattering method based on Mie scattering theory. Specifically, a particle size distribution of an inorganic filler can be made based on a volume basis by a laser diffraction scattering particle size distribution measuring device, and its median particle size is measured as the average particle size. The determination sample can be used by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a tube bottle and dispersing it by ultrasonic waves for 10 minutes. The sample is measured using a laser diffraction particle size distribution measuring instrument with a blue and red light source wavelength, and a flow cell method is used to measure the volume-based particle size distribution of the inorganic filler. The average particle size is calculated based on the obtained particle size distribution as the median particle size. Examples of laser diffraction particle size distribution measuring instruments include the "LA-960" manufactured by Horiba, Ltd.
[0103] The specific surface area of the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, 3m 2 / g or above or 5m 2 The upper limit of the specific surface area is not particularly limited, but is preferably 100 m 2 / g or less, preferably 80m 2 / g or less, more preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 The specific surface area of the inorganic filler can be obtained by adsorbing nitrogen gas on the sample surface using a specific surface area measuring apparatus (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method and calculating the specific surface area by the BET multipoint method.
[0104] The inorganic filler is preferably surface treated by a suitable surface treatment agent. By carrying out surface treatment, the moisture resistance and dispersibility of the inorganic filler can be improved. As the surface treatment agent, the silane coupling agents such as vinyl silane coupling agent, epoxy silane coupling agent, styrene-based silane coupling agent, (methyl) acrylic silane coupling agent, amino-based silane coupling agent, isocyanurate-based silane coupling agent, urea-based silane coupling agent, mercapto-based silane coupling agent, isocyanate-based silane coupling agent, anhydride-based silane coupling agent, non-silane coupling-alkoxysilane compounds such as methyltrimethoxysilane, phenyltrimethoxysilane, silazane compounds etc. can be enumerated. The surface treatment agent can be used alone or in combination of two or more.
[0105] Commercially available products of the surface treatment agent include, for example, “KBM403” (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM803” (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBE903” (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM573” (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., and “SZ-31” (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0106] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface treated with 0.2 to 5% by mass of the surface treatment agent.
[0107] The degree of surface treatment by the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is preferably 0.02 mg / m 2 More than 0.1 mg / m 2 More than 0.2 mg / m 2 On the other hand, from the viewpoint of preventing the increase of the melt viscosity of the resin composition or the melt viscosity in the sheet form, it is preferably 1.0 mg / m 2 Below, more preferably 0.8mg / m 2 Below, more preferably 0.5 mg / m 2Below. The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is cleaned with a solvent (for example, methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK is added as a solvent to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid component, the amount of carbon per unit surface area of the inorganic filler can be measured using a carbon analyzer. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd. or the like can be used.
[0108] In the combination with resin X and Y, from the viewpoint of the cured product with low dielectric loss tangent, good elongation, excellent uniformity, when the non-volatile component in the resin combination is set to 100 mass %, the content of the inorganic filler in the resin combination is preferably more than 50 mass %, more preferably more than 55 mass %, further more preferably more than 60 mass %. As previously mentioned, in the system comprising resin Y, if in order to achieve low dielectric loss tangent and high coordination of inorganic filler, there is a tendency to return to the cured product of elongation and poor uniformity. In contrast, if the present invention of resin X is used in combination with resin Y, the content of inorganic filler can be further improved while suppressing elongation and uniformity variation. For example, when the non-volatile component in the resin combination is set to 100 mass %, the content of the inorganic filler in the resin combination can be increased to more than 62 mass %, more than 64 mass %, more than 65 mass %, more than 66 mass % or more than 68 mass %. The upper limit of the content of the inorganic filler is not particularly limited, and can be, for example, 90% by mass or less, 85% by mass or less, or the like.
[0109] <Thermosetting resin> The resin composition of the present invention may further contain a thermosetting resin.
[0110] The thermosetting resin is not particularly limited, and examples thereof include epoxy resins, benzocyclobutene resins, epoxy acrylate resins, urethane acrylate resins, polyurethane resins, cyanate resins, polyimide resins, benzoxazine resins, unsaturated polyester resins, melamine resins, and silicone resins. Among these, in combination with resins X and Y, it is preferred to include an epoxy resin from the viewpoint of producing a cured product having a low dielectric loss tangent, good elongation, and excellent uniformity.
[0111] For epoxy resin, as long as there are more than one, preferably more than two epoxy groups in one molecule, its type is not particularly limited. As epoxy resin, for example, bisphenol type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butylcatechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin with butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, epoxy resin containing spiro ring, cyclohexane type epoxy resin, cyclohexanedimethanol type epoxy resin, naphthyl ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin can be enumerated. Bisphenol-type epoxy resins refer to epoxy resins with a bisphenol structure, and examples include bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, and bisphenol AF epoxy resins. Biphenyl-type epoxy resins refer to epoxy resins with a biphenyl structure; the biphenyl structure may have substituents such as alkyl, alkoxy, and aryl groups. Therefore, biphenyl-type epoxy resins and biphenyl aralkyl epoxy resins are also included in biphenyl-type epoxy resins.
[0112] Epoxy resins can be classified into epoxy resins that are liquid at a temperature of 20°C (hereinafter referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter referred to as "solid epoxy resins"). The resin composition of the present invention may contain only liquid epoxy resin, only solid epoxy resin, or a combination of liquid epoxy resin and solid epoxy resin.
[0113] The liquid epoxy resin is preferably one having two or more epoxy groups in one molecule.
[0114] As liquid epoxy resins, preferred are GLYCIROL type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexanedimethanol type epoxy resins, cyclic aliphatic glycidyl ethers, and epoxy resins having a butadiene structure.
[0115] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX Co., Ltd., "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" manufactured by DIC Corporation (naphthalene-type epoxy resins), "828US", "828EL", and "825" manufactured by Mitsubishi Chemical Corporation (bisphenol A-type epoxy resins), "jER807" and "1750" manufactured by Mitsubishi Chemical Corporation (bisphenol F-type epoxy resins), "jER152" manufactured by Mitsubishi Chemical Corporation (phenol novolac-type epoxy resin), and "HP4032" manufactured by DIC Corporation (naphthalene-type epoxy resins). Co., Ltd.'s "630", "630LSD", and "604" (glycidylamine epoxy resins), ADEKA Corporation's "ED-523T" (GLYCIROL epoxy resin), ADEKA Corporation's "EP-3950L" and "EP-3980S" (glycidylamine epoxy resins), ADEKA Corporation's "EP-4088S" (dicyclopentadiene epoxy resin), Nippon Steel Chemicals Co., Ltd.'s "ZX1059" (a mixture of bisphenol A and bisphenol F epoxy resins), Nagase "EX-721" (glycidyl ester type epoxy resin) manufactured by ChemteX Corporation, "EX-991L" (epoxy resin containing an alkylene oxide skeleton and a butadiene skeleton) manufactured by Nagase ChemteX Corporation, "CELLOXIDE 2021P" (alicyclic epoxy resin with an ester skeleton) manufactured by Daicel Corporation, "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins with a butadiene structure), "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemicals Co., Ltd., "EG-280" (epoxy resin containing a fluorene structure) manufactured by Osaka Gas Chemical Co., Ltd., Nagase "EX-201" (cyclic aliphatic glycidyl ether) manufactured by ChemteX Corporation, etc.
[0116] The solid epoxy resin is preferably a solid epoxy resin having three or more epoxy groups in one molecule, more preferably an aromatic solid epoxy resin having three or more epoxy groups in one molecule.
[0117] As solid epoxy resins, preferred are biphenylol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, naphthol novolac-type epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, naphthyl ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, phenol aralkyl-type epoxy resins, tetraphenylethane-type epoxy resins, and phenolphthalimidine-type epoxy resins.
[0118] Specific examples of solid epoxy resins include “HP4032H” (naphthalene-type epoxy resin) manufactured by DIC Corporation, “HP-4700” and “HP-4710” (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation, “N-690” (cresol novolac-type epoxy resin) manufactured by DIC Corporation, “N-695” (cresol novolac-type epoxy resin) manufactured by DIC Corporation, “HP-7200”, “HP-7200HH”, “HP-7200H” and “HP-7200L” (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation, and “HP-7200HH” and “HP-7200H” (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation. "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP-6000", "HP-6000L" (naphthyl ether type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., "ESN475V" and "ESN4100V" (naphthalene-type epoxy resins) manufactured by Nippon Steel Chemicals Co., Ltd., "ESN485" (naphthol-type epoxy resin) manufactured by Nippon Steel Chemicals Co., Ltd., "ESN375" (dihydroxynaphthalene-type epoxy resin) manufactured by Nippon Steel Chemicals Co., Ltd., "YX4000H", "YX4000", "YX4000HK", and "YL7890" (bimethylol-type epoxy resins) manufactured by Mitsubishi Chemical Corporation, "YL6121" (biphenyl-type epoxy resin) manufactured by Mitsubishi Chemical Corporation, and "YX8800" (anthracene-type epoxy resin) manufactured by Mitsubishi Chemical Corporation. , "YX7700" (phenol aralkyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd., "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation, "WHR991S" (phenol benzopyrrolidone type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These resins may be used alone or in combination of two or more.
[0119] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, the mass ratio thereof (liquid epoxy resin:solid epoxy resin) is preferably from 10:1 to 1:50, more preferably from 5:1 to 1:20, further preferably from 2:1 to 1:10, particularly preferably from 1:1 to 1:3.
[0120] The epoxy equivalent weight of the epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 60 g / eq. to 2000 g / eq., further preferably 70 g / eq. to 1000 g / eq., and even more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent weight is the mass of the resin per equivalent of epoxy groups. This epoxy equivalent weight can be measured in accordance with JIS K7236.
[0121] The weight average molecular weight of the epoxy resin is preferably from 100 to 5000, more preferably from 250 to 3000, further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured as a value in terms of polystyrene by gel permeation chromatography (GPC).
[0122] When the resin composition of the present invention includes a thermosetting resin, the content of the thermosetting resin in the resin composition is not particularly limited. When the resin component in the resin composition is set to 100% by mass, it is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 12% by mass or more, 14% by mass or more, or 15% by mass or more. The upper limit of this content is not particularly limited and can be determined based on the characteristics required for the resin composition, and can be, for example, 60% by mass or less, 50% by mass or less, or 40% by mass or less.
[0123] Curing agent The resin composition of the present invention may further contain a curing agent.
[0124] As a curing agent, there is no particular limitation, and examples thereof include active ester curing agents, phenol curing agents, naphthol curing agents, carbodiimide curing agents, acid anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate curing agents, and thiol curing agents. One type of curing agent can be used alone, or two or more types can be used in combination. From the viewpoint of being able to enjoy the effects of the present invention more, the curing agent is preferably selected from one or more of active ester curing agents, phenol curing agents, and carbodiimide curing agents.
[0125] As active ester curing agent, a compound having more than one active ester group in one molecule can be used. Wherein, as active ester curing agent, preferably a compound having more than two reactive ester groups in one molecule such as esters of phenolic esters, thiophenolic esters, N-hydroxylamine esters, and heterocyclic hydroxy compounds. The active ester curing agent is preferably a curing agent obtained by the condensation reaction of a carboxylic acid compound and / or a thiocarboxylic acid compound with a hydroxy compound and / or a thiol compound. Particularly from the viewpoint of improving heat resistance, it is preferably an active ester curing agent derived from a carboxylic acid compound, more preferably an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound, and further more preferably an active ester curing agent obtained from a carboxylic acid compound and an aromatic hydroxy compound.
[0126] As the carboxylic acid compound, any of aromatic carboxylic acid compounds and aliphatic carboxylic acid compounds can be used, and examples thereof include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and halides thereof.
[0127] Examples of aromatic hydroxy compounds include (i) addition polymerization products of unsaturated aliphatic cyclic compounds containing two double bonds per molecule and phenols, (ii) various bisphenol compounds, (iii) aromatic polyols having two or more hydroxyl groups bonded to carbon atoms on the aromatic ring, and (iv) aromatic monohydric alcohols having one hydroxyl group bonded to a carbon atom on the aromatic ring. Examples of addition polymerization products of unsaturated aliphatic cyclic compounds and phenols include addition polymerization products of unsaturated aliphatic cyclic compounds such as dicyclopentadiene, tetrahydroindene, norbornadiene, limonene, and vinylcyclohexene and phenols which may have a substituent (e.g., phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, and halogenated phenols). Specific examples include dicyclopentadiene-phenol addition polymerization products. Examples of the bisphenol compound include bisphenol A, bisphenol F, bisphenol AF, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, and bisphenol M. Examples of the aromatic polyol having two or more hydroxyl groups bonded to carbon atoms on an aromatic ring include hydroquinone, resorcinol, catechol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, and phenolic novolac resin. Examples of the aromatic monohydric alcohol having one hydroxyl group bonded to a carbon atom on the aromatic ring include phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halogenated phenols, naphthol, methylnaphthol, dimethylnaphthol, ethylnaphthol, propylnaphthol, vinylnaphthol, allylnaphthol, phenylnaphthol, benzylnaphthol, and halogenated naphthols.
[0128] Preferred specific examples of active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, active ester compounds containing a naphthalene structure, active ester compounds containing acetylated products of novolac resins, and active ester compounds containing benzoylated products of novolac resins. Among these, active ester compounds containing a naphthalene structure and active ester compounds containing a dicyclopentadiene-type diphenol structure are more preferred. "Dicyclopentadiene-type diphenol structure" refers to a divalent structural unit composed of phenylene-dicyclopentylene-phenylene.
[0129] Examples of commercially available active ester curing agents include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation), which are active ester compounds containing a dicyclopentadiene-type diphenol structure; and "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", and "HPC-8151-62T" (manufactured by DIC Corporation), which are active ester compounds containing a naphthalene structure. 0-62T", "EXB-8" (manufactured by DIC Corporation), "EXB9401" (manufactured by DIC Corporation) as a phosphorus-containing active ester compound, "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound containing an acetylated product of a linear phenolic resin, "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester compounds containing a benzoylated product of a linear phenolic resin, and "PC1300-02-65MA" (manufactured by Airwater Corporation) as an active ester compound containing a styryl group and a naphthalene structure.
[0130] As phenol curing agent and naphthol curing agent, from the viewpoint of heat resistance and water resistance, preferably the phenol curing agent with phenolic structure or the naphthol curing agent with phenolic structure.In addition, from the viewpoint of the insulating barrier that can realize the good adhesion strength (peel strength) of conductor layer, preferably nitrogenous phenol curing agent or nitrogenous naphthol curing agent, more preferably the phenol curing agent containing triazine skeleton or the naphthol curing agent containing triazine skeleton.Wherein, from the viewpoint that makes heat resistance, water resistance and with the adhesion strength height of conductor layer satisfy, preferably the phenol novolac resin containing triazine skeleton or the naphthol novolac resin containing triazine skeleton.
[0131] Specific examples of phenol-based curing agents and naphthol-based curing agents include "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemicals Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; and "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", and "SN-375" manufactured by Nippon Steel Chemicals Co., Ltd. , "SN-395", "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P" made by DIC Co., Ltd. , "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", "KA-1165", "GDP-6115L", "GDP-6115H", "ELPC75" made by Kunei Chemical Co., Ltd., etc.
[0132] Examples of the carbodiimide curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, and examples thereof include aliphatic biscarbodiimides such as tetramethylene-bis(tert-butylcarbodiimide) and cyclohexanebis(methylene-tert-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide); Polycarbodiimides; aromatic polycarbodiimides such as poly(phenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), poly[methylenebis(methylphenylene)carbodiimide], and the like.
[0133] Examples of commercially available carbodiimide curing agents include "CARBODILITE V-02B", "CARBODILITE V-03", "CARBODILITE V-04K", "CARBODILITE V-07", and "CARBODILITE V-09" manufactured by Nisshinbo Chemical Co., Ltd., and "Stabaxol P", "Stabaxol P400", and "Hycasyl 510" manufactured by LANXESS.
[0134] As the acid anhydride curing agent, there can be mentioned a curing agent having one or more acid anhydride groups in one molecule, preferably a curing agent having two or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, dicarboxylic anhydride, Polymer-type acid anhydrides such as benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furyl)-naphtho[1,2-c]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and styrene-maleic acid resin obtained by copolymerizing styrene with maleic acid. Commercially available products of anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by Shin Nippon Chemical Co., Ltd., "YH306" and "YH307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Resonac Co., Ltd., and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Cray Valley Co., Ltd.
[0135] As the amine curing agent, there can be mentioned a curing agent having one or more, preferably two or more, amino groups in one molecule, for example, aliphatic amines, polyetheramines, alicyclic amines, aromatic amines, etc., wherein, from the viewpoint of exerting the desired effect of the present invention, aromatic amines are preferred. The amine curing agent is preferably a primary amine or a secondary amine, more preferably a primary amine. As specific examples of the amine curing agent, there can be mentioned 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, metaphenylenediamine, metaphenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxybenzidine) phenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. As the amine curing agent, commercially available products can be used, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "EPICURE W" manufactured by Mitsubishi Chemical Corporation.
[0136] Specific examples of benzoxazine curing agents include “JBZ-OP100D” and “ODA-BOZ” manufactured by JFE Chemical Corporation, “HFB2006M” manufactured by Showa Highpolymer Co., Ltd., and “Pd” and “Fa” manufactured by Shikoku Chemicals Co., Ltd.
[0137] Examples of cyanate curing agents include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by triazinization of a portion of these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Lonza Japan (both are novolac-type multifunctional cyanate resins), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate is triazine-treated to form a trimer), etc.
[0138] Examples of the thiol-based curing agent include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0139] The reactive group equivalent weight of the curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent weight is the mass of the curing agent per 1 equivalent of reactive groups.
[0140] From the viewpoint of bringing a cured product with low dielectric loss tangent, the curing agent preferably comprises an active ester curing agent. When the curing agent comprises an active ester curing agent, when the non-volatile component in the curing agent is set to 100% by mass, the content of the active ester curing agent is preferably 30% by mass or more, more preferably 40% by mass or more, further more preferably 50% by mass or more or 60% by mass or more, and its upper limit can be 100% by mass, and can be set to, for example, 98% by mass or less, 95% by mass or less, or 90% by mass or less.
[0141] When the resin combination of the present invention includes a curing agent, the content of the curing agent in the resin combination is not particularly limited. When the resin component in the resin combination is set to 100 mass %, it is preferably more than 3 mass %, more preferably more than 5 mass %, further more preferably more than 10 mass %, more than 15 mass % or more than 20 mass %. The upper limit of the content of the curing agent is preferably below 60 mass %, more preferably below 50 mass %, below 45 mass %, below 40 mass % or below 35 mass %.
[0142] Curing accelerator The resin composition of the present invention may further contain a curing accelerator. By containing a curing accelerator, the curing time and curing temperature can be effectively adjusted.
[0143] Examples of curing accelerators include phosphorus curing accelerators, urea curing accelerators, guanidine curing accelerators, imidazole curing accelerators, metal curing accelerators, and amine curing accelerators. From the perspective of being able to enjoy the effects of the present invention more effectively, the curing accelerator preferably comprises an amine curing accelerator or an imidazole curing accelerator. One curing accelerator may be used alone, or two or more may be used in combination.
[0144] Phosphorus curing accelerators include, for example, tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogen hexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, di-tert-butylmethylphosphonium tetraphenylborate and other aliphatic phosphonium salts; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, para- Aromatic phosphonium salts such as tolyltriphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone addition reactants such as triphenylphosphine-p-benzoquinone addition reactants; tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, diphenylphosphine aliphatic phosphines such as tert-butyl (2-butenyl) phosphine, di-tert-butyl (3-methyl-2-butenyl) phosphine, and tricyclohexyl phosphine; dibutylphenyl phosphine, di-tert-butylphenyl phosphine, methyldiphenyl phosphine, ethyldiphenyl phosphine, butyldiphenyl phosphine, diphenylcyclohexyl phosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tri(4-ethylphenyl)phosphine, tri(4-propylphenyl)phosphine, tri(4-isopropylphenyl)phosphine, tri(4-butylphenyl)phosphine, tri(4-tert-butylphenyl)phosphine, tri(2,4-dimethylphenyl)phosphine, tri(2,5-dimethylphenyl)phosphine, tri(2 ,6-dimethylphenyl)phosphine, tri(3,5-dimethylphenyl)phosphine, tri(2,4,6-trimethylphenyl)phosphine, tri(2,6-dimethyl-4-ethoxyphenyl)phosphine, tri(2-methoxyphenyl)phosphine, tri(4-methoxyphenyl)phosphine, tri(4-ethoxyphenyl)phosphine, tri(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, 2,2'-bis(diphenylphosphino)diphenyl ether and the like.
[0145] Examples of the urea curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1, Aromatic dimethylureas such as 1-dimethylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluenebisdimethylurea].
[0146] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.
[0147] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1') imidazole compounds such as 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins.
[0148] As the imidazole curing accelerator, commercially available products can be used, and examples thereof include "1B2PZ," "2E4MZ," "2MZA-PW," "2MZ-OK," "2MA-OK," "2MA-OK-PW," "2P4MZ," "2PHZ," "2PHZ-PW," "C11Z," "C11Z-CN," "C11Z-CNS," and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd., and "P200-H50" manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more.
[0149] Examples of metal curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt (II) acetylacetonate and cobalt (III) acetylacetonate, organocopper complexes such as copper (II) acetylacetonate, organozinc complexes such as zinc (II) acetylacetonate, organoferric complexes such as iron (III) acetylacetonate, organonickel complexes such as nickel (II) acetylacetonate, and organomanganese complexes such as manganese (II) acetylacetonate. Examples of organometallic salts include zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0150] Examples of amine curing accelerators include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine (DMAP), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo[5.4.0]undecene. Amine curing accelerators that are commercially available may be used, and examples thereof include "MY-25" manufactured by Ajinomoto Fine Chemicals Co., Ltd.
[0151] When the resin composition of the present invention includes a curing accelerator, the content of the curing accelerator in the resin composition is not particularly limited. When the resin component in the resin composition is set to 100% by mass, it is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and further more preferably 0.05% by mass or more. The upper limit is preferably 3% by mass or less, more preferably 2% by mass or less, 1.5% by mass or less, or 1% by mass or less.
[0152] <Radical polymerization initiator> The resin composition of the present invention may further contain a radical polymerization initiator. The radical polymerization initiator may be used alone or in combination of two or more.
[0153] Examples of the radical polymerization initiator include peroxide-based radical polymerization initiators and azo-based radical polymerization initiators. Among them, peroxide-based radical polymerization initiators are preferred.
[0154] Examples of the peroxide-based radical polymerization initiator include hydroperoxide compounds such as 1,1,3,3-tetramethylbutyl hydroperoxide; dialkyl peroxide compounds such as tert-butyl isopropyl peroxide, di-tert-butyl peroxide, di-tert-hexyl peroxide, dicumyl peroxide, 1,4-bis(1-tert-butylperoxy-1-methylethyl)benzene, and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; dilauroyl peroxide, didecanoyl peroxide, dicyclohexyl peroxydicarbonate, and bis(4-tert-butylcyclohexyl)peroxydicarbonate. Peroxy diacyl compounds such as oxydicarbonates; peroxy ester compounds such as tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxylaurate, 1,1-dimethylpropyl 2-ethylperoxyhexanoate, tert-butyl 2-ethylperoxyhexanoate, tert-butyl 3,5,5-trimethylperoxyhexanoate, tert-butyl peroxy-2-ethylhexyl monocarbonate, and tert-butyl peroxymaleate; etc.
[0155] Examples of commercially available radical polymerization initiators include "PERBUTYL C", "PERBUTYL A", "PERBUTYL P", "PERBUTYL L", "PERBUTYL O", "PERBUTYL ND", "PERBUTYL Z", "PERBUTYL I", "PERCUMYL P", "PERCUMYL D", "PERHEXYL D", "PERHEXYL A", "PERHEXYL I", "PERHEXYL Z", "PERHEXYL ND", "PERHEXYL O", and "PERHEXYL PV" manufactured by NOF Corporation.
[0156] When the resin composition of the present invention includes a radical polymerization initiator, the content of the radical polymerization initiator in the resin composition is not particularly limited. When the resin component in the resin composition is set to 100% by mass, it is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, further more preferably 0.1% by mass or more, and its upper limit is preferably 3% by mass or less, more preferably 2% by mass or less, further more preferably 1% by mass or less or 0.5% by mass or less.
[0157] Optional additives The resin composition of the present invention may further contain any additives. Examples of such additives include thermoplastic resins such as phenoxy resins, polyvinyl acetal resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, and polyester resins; organic fillers such as rubber particles; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, olive green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and thiophene; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentonite and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion enhancers such as urea silane; triazole-based adhesion imparting agents; Adhesion-imparting agents such as azole adhesion-imparting agents and triazine adhesion-imparting agents, antioxidants such as hindered phenol antioxidants, fluorescent whitening agents such as stilbene derivatives, surfactants such as fluorine-based surfactants and silicone-based surfactants, flame retardants such as phosphorus-based flame retardants (such as phosphate compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (such as melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (such as antimony trioxide), dispersants such as phosphate-based dispersants, polyoxyalkylene dispersants, acetylene dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants, stabilizers such as borate stabilizers, titanate stabilizers, aluminate stabilizers, zirconate stabilizers, isocyanate stabilizers, carboxylic acid stabilizers, and carboxylic anhydride stabilizers, etc. The content of the additives can be determined according to the properties required for the resin composition.
[0158] Organic solvents The resin composition of the present invention may further contain an organic solvent as a volatile component. Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol ethyl ether acetate. Ether ester solvents such as methyl acetate, γ-butyrolactone, and methyl methoxypropionate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The organic solvents may be used alone or in combination.
[0159] Resin combination of the present invention for example can be manufactured as follows: in any preparation container, add inorganic filler, resin X, Y containing oligophenylene ether skeleton in any order and / or partly or entirely simultaneously, and the thermosetting resin, curing agent, curing accelerator, free radical polymerization initiator, other additives and organic solvent adopted as required and mix.In addition, add each composition and in the process of mixing, can suitably set temperature, can part time or always heat and / or cool.In addition, in adding and in the process of mixing or thereafter, thermosetting resin composition can be stirred or vibrated with stirring devices such as mixers or oscillating devices and be evenly dispersed.In addition, while stirring or vibrating, can deaerate under low pressure conditions such as under vacuum.
[0160] As described above, the resin composition of the present invention comprising an inorganic filler and resins X and Y containing an oligophenylene ether skeleton can provide a cured product having a low dielectric loss tangent, good elongation, and excellent uniformity.
[0161] In one embodiment, the cured product of the resin composition of the present invention exhibits a low dielectric loss tangent (Df). For example, when measured under the conditions of 5.8 GHz and 23°C as described in the "Measurement of Dielectric Loss Tangent" column described below, the cured product of the resin composition of the present invention can have a dielectric loss tangent (Df) of preferably 0.0040 or less, more preferably 0.0038 or less, further preferably 0.0036 or less, further more preferably 0.0034 or less, and particularly preferably 0.0032 or less.
[0162] In one embodiment, the cured product of the resin composition of the present invention has a characteristic of exhibiting good elongation. For example, when measured under the conditions based on JIS K7127 as described in the "Evaluation of Elongation" column described later, the elongation (elongation at break) of the cured product of the resin composition of the present invention is preferably 0.9% or more or 1.0% or more, more preferably 1.2% or more or 1.3% or more, and further preferably 1.5% or more or 1.6% or more. The upper limit is not particularly limited and can generally be 5% or less, 4% or less, 3% or less, etc.
[0163] As mentioned above, the resin composition of the present invention can bring a cured product with low dielectric loss tangent, good elongation and excellent uniformity. Therefore, the resin composition of the present invention can be used as a resin composition for forming a sealing layer on a semiconductor chip in semiconductor chip packaging (resin composition for semiconductor sealing). The resin composition of the present invention can also be used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for insulating layer of a printed wiring board), and can be used more preferably as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for interlayer insulating layer of a printed wiring board). The resin composition of the present invention can also be used well in the case where the printed wiring board is a component built-in circuit board. The resin composition of the present invention can also be used well as a resin composition for forming an insulating layer of a rewiring substrate in semiconductor chip packaging (resin composition for insulating layer of a rewiring substrate). It should be noted that in the present invention, the printed wiring board and the rewiring substrate are also collectively referred to as "circuit substrate", so the resin composition of the present invention can be used well as a resin composition for insulating layer of a circuit substrate.
[0164] The resin composition of the present invention can be widely used in applications requiring a resin composition, such as resin sheets, sheet-like laminates such as prepregs, solder resists, underfills, die bonding materials, hole-filling resins, sealing resins, and component embedding resins.
[0165] [Sheet-like laminated materials (resin sheets, prepregs)] The resin composition of the present invention may be used as it is, or may be used in the form of a sheet-like laminate containing the resin composition.
[0166] As the sheet-like laminated material, the following resin sheets and prepregs are preferred.
[0167] In one embodiment, the resin sheet includes a support and a layer of a resin composition provided on the support (hereinafter referred to as "resin composition layer"), and the resin composition layer is characterized in that it is formed from the resin composition of the present invention.
[0168] About the thickness of resin composition layer, preferred value is different according to purpose, can be suitably determined according to purpose.For example, from the viewpoint of the thinning of printed wiring board and semiconductor chip package, the thickness of resin composition layer is preferably less than 400 μm, less than 300 μm, less than 200 μm, less than 100 μm, less than 80 μm, less than 60 μm, less than 50 μm, less than 40 μm or less than 30 μm.The lower limit of the thickness of resin composition layer is not particularly limited, and can usually be set to more than 1 μm, more than 5 μm, etc.
[0169] Examples of the support include thermoplastic resin films, metal foils, and release papers, with thermoplastic resin films and metal foils being preferred. Therefore, in a preferred embodiment, the support is a thermoplastic resin film or a metal foil.
[0170] When a thermoplastic resin film is used as a support, examples of the thermoplastic resin include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylics such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, and polyimide. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0171] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, with copper foil being preferred. The copper foil may be a foil made of copper alone or an alloy of copper and other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0172] The support may be subjected to matte treatment, corona discharge treatment, or antistatic treatment on the surface bonded to the resin composition layer. In addition, as the support, a support with a release layer having a release layer on the surface bonded to the resin composition layer may be used. As a release agent for the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins may be cited. Commercially available products may be used for the support with a release layer, for example, "SK-1," "AL-5," and "AL-7" manufactured by Lintec Co., Ltd., "LUMIRROR T60" manufactured by Toray Industries, Ltd., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Co., Ltd., which are PET films having a release layer with an alkyd resin release agent as the main component, may be cited.
[0173] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the entire thickness of the support with a release layer is preferably within the above range.
[0174] When using a metal foil as a support, a metal foil with a supporting substrate, in which a removable supporting substrate is bonded to a thin metal foil, can be used. In one embodiment, the metal foil with a supporting substrate comprises a supporting substrate, a release layer provided on the supporting substrate, and a metal foil provided on the release layer. When using a metal foil with a supporting substrate as a support, the resin composition layer is provided on the metal foil.
[0175] In the metal foil with a supporting substrate, the material of the supporting substrate is not particularly limited, and examples thereof include copper foil, aluminum foil, stainless steel foil, titanium foil, and copper alloy foil. When copper foil is used as the supporting substrate, it may be electrolytic copper foil or rolled copper foil. Furthermore, the release layer is not particularly limited as long as it allows the metal foil to be released from the supporting substrate. Examples thereof include alloy layers of elements selected from Cr, Ni, Co, Fe, Mo, Ti, W, and P, and organic films.
[0176] In the metal foil with a supporting substrate, the material of the metal foil is preferably, for example, copper foil or copper alloy foil.
[0177] In the metal foil with a supporting substrate, the thickness of the supporting substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, more preferably in the range of 10 μm to 100 μm. The thickness of the metal foil can be, for example, in the range of 0.1 μm to 10 μm.
[0178] In one embodiment, the resin sheet may further include an arbitrary layer as needed. As the arbitrary layer, for example, a protective film provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the side opposite to the support) can be cited. The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress the adhesion of garbage or the formation of damage on the surface of the resin composition layer.
[0179] The resin sheet can be produced, for example, by directly preparing a liquid resin composition or preparing a resin varnish by dissolving the resin composition in an organic solvent, applying the varnish onto a support using a die coater or the like, and drying the varnish to form a resin composition layer.
[0180] Examples of the organic solvent include the same organic solvents as those described as components of the resin composition. The organic solvents may be used alone or in combination of two or more.
[0181] Drying can be carried out by known methods such as heating and blowing hot air. The drying conditions are not particularly limited, but drying is performed under conditions such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying conditions vary depending on the boiling point of the organic solvent in the resin composition or resin varnish. For example, when using a resin composition or resin varnish containing 30% to 60% by mass of an organic solvent, the resin composition layer can be formed by drying at 50°C to 150°C for 3 to 10 minutes.
[0182] The resin sheet can be stored in a roll. If the resin sheet has a protective film, it can be used by peeling off the protective film.
[0183] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber base material with the resin composition of the present invention.
[0184] The sheet-like fiber substrate used for the prepreg is not particularly limited, and materials commonly used as prepreg substrates, such as glass cloth, aramid nonwoven fabric, and liquid crystal polymer nonwoven fabric, can be used. From the perspective of reducing the thickness of printed wiring boards and semiconductor chip packages, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited, but is generally 10 μm or greater.
[0185] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0186] The thickness of the prepreg can be set to the same range as that of the resin composition layer in the above-mentioned resin sheet.
[0187] The sheet-like laminated material of the present invention can be preferably used to form a sealing layer on a semiconductor chip in semiconductor chip packaging (for semiconductor sealing). The sheet-like laminated material of the present invention can also be preferably used to form an insulating layer of a printed wiring board (for insulating layer of a printed wiring board), and can be more preferably used to form an interlayer insulating layer of a printed wiring board (for interlayer insulating layer of a printed wiring board). The sheet-like laminated material of the present invention can also be preferably used to form an insulating layer of a rewiring substrate in semiconductor chip packaging (for insulating layer of a rewiring substrate). That is, the sheet-like laminated material of the present invention can also be preferably used as an insulating layer of a circuit substrate.
[0188] [Semiconductor chip packaging] The semiconductor chip package of the present invention comprises a cured product of the resin composition of the present invention.
[0189] In one embodiment, the semiconductor chip package of the present invention comprises a package substrate, a semiconductor chip mounted on the substrate, and a cured product of the resin composition of the present invention that seals at least a portion of the semiconductor chip. This embodiment is hereinafter referred to as "Embodiment A."
[0190] In Embodiment A, a conventionally known substrate for forming a semiconductor chip package can be used as the package substrate, and it may be manufactured in the same manner as a printed wiring board described later, for example.
[0191] The bonding conditions between the package substrate and the semiconductor chip may be any conditions that allow for conductive connection between the terminal electrodes of the semiconductor chip and the circuit wiring of the substrate. For example, conditions used in flip-chip mounting of semiconductor chips may be used.
[0192] As a bonding method, for example, a method of pressing a semiconductor chip onto a substrate can be cited. As a bonding condition, the bonding temperature is usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and the bonding time is usually in the range of 1 second to 60 seconds (preferably 5 seconds to 30 seconds). In addition, as a bonding method, for example, a method of placing a semiconductor chip on a substrate and performing reflow soldering to bond the semiconductor chip can also be cited. The reflow soldering condition can be set to a range of 120°C to 300°C.
[0193] After the semiconductor chip is bonded to the substrate, the gap between the semiconductor chip and the substrate can be filled with an underfill. The resin composition of the present invention can also be used as the underfill. In such a case, the semiconductor chip package of the present invention includes an underfill formed from a cured product of the resin composition of the present invention.
[0194] The sealing of the semiconductor chip can be performed by the same method as step (3) in embodiment B described later. As mentioned above, the resin composition of the present invention is useful as a sealing material for the semiconductor chip. In such a case, the semiconductor chip package of the present invention includes a sealing layer formed from a cured product of the resin composition of the present invention.
[0195] The resin composition of the present invention can be used as a mold underfill to simultaneously fill the gap between a semiconductor chip and a substrate and seal the semiconductor chip.
[0196] When a semiconductor chip package is produced using the resin composition of the present invention, the resin composition of the present invention may be used as a liquid resin composition or in the form of a sheet-like laminate as described above.
[0197] In another embodiment (hereinafter also referred to as "embodiment B"), the semiconductor chip package of the present invention can be manufactured, for example, using the resin composition of the present invention by a method including the following steps (1) to (6). In order to form the sealing layer of step (3) or the redistribution forming layer of step (5), the resin composition of the present invention can be used. Below, an example of using the resin composition to form the sealing layer and the redistribution forming layer is shown, but the technology for forming the sealing layer and the redistribution forming layer of the semiconductor chip package is well known, and anyone skilled in the art can use the resin composition of the present invention to manufacture a semiconductor chip package according to the known technology. (1) a step of laminating a temporary fixing film on a substrate; (2) A process of temporarily fixing the semiconductor chip on a temporary fixing film; (3) a step of forming a sealing layer on a semiconductor chip; (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip; (5) a step of forming a rewiring forming layer as an insulating layer on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off; and (6) A step of forming a rewiring layer as a conductive layer on the rewiring formation layer.
[0198] -Process (1)- The material used for the substrate is not particularly limited. Examples of the substrate include silicon wafers, glass wafers, glass substrates, metal substrates such as copper, titanium, stainless steel, and cold-rolled steel sheets (SPCC), substrates obtained by impregnating glass fibers with epoxy resins and then heat-curing (e.g., FR-4 substrates), and substrates formed from bismaleimide triazine resins (BT resins).
[0199] The temporary fixing film is not particularly limited as long as it is a material that can be peeled from the semiconductor chip in step (4) and can temporarily fix the semiconductor chip. Commercially available products can be used as temporary fixing films. Examples of commercially available products include REVALPHA manufactured by Nitto Denko Corporation.
[0200] -Process (2)- The semiconductor chip is temporarily fixed to the temporary fixing film by bonding its electrode pad surface to the temporary fixing film. Temporary fixing of the semiconductor chip can be performed using a known device such as a flip-chip bonder or a chip mounter. The layout and number of semiconductor chips can be appropriately determined based on the shape and size of the temporary fixing film, the target production volume of semiconductor packages, and other factors. For example, the chips can be arranged in a matrix of multiple rows and columns for temporary fixing.
[0201] -Process (3)- The resin composition of the present invention is applied as a liquid composition onto a semiconductor chip and cured (e.g., thermally cured) to form a sealing layer. Alternatively, the resin composition of the present invention can be laminated onto a semiconductor chip in the form of the above-mentioned resin sheet and cured (e.g., thermally cured) to form a sealing layer.
[0202] When used in the form of a resin sheet, the semiconductor chip and the resin sheet can be laminated by removing the protective film from the resin sheet and then heat-pressing the resin sheet onto the semiconductor chip from the support side. Lamination of the semiconductor chip and the resin sheet can be performed by vacuum lamination. The lamination conditions are the same as those described later in the method for producing a printed wiring board, and the preferred ranges are also the same.
[0203] After lamination, the resin composition is thermally cured to form a sealing layer. The thermal curing conditions are the same as those described later in the method for producing a printed wiring board.
[0204] The support of the resin sheet may be peeled off after the resin sheet is laminated on the semiconductor chip and thermally cured, or the support may be peeled off before the resin sheet is laminated on the semiconductor chip.
[0205] When the resin composition of the present invention is applied as a liquid composition to form a sealant layer, the coating conditions can be the same as those for forming the resin composition layer described for the resin sheet of the present invention. By using the resin composition of the present invention, good fluidity can be achieved at the coating / molding temperature.
[0206] - Process (4) - The method of peeling the substrate and the temporary fixing film can be appropriately changed according to the material of the temporary fixing film, and examples thereof include a method of peeling by heating and foaming (or expanding) the temporary fixing film, and a method of peeling by irradiating the substrate with ultraviolet rays to reduce the adhesive force of the temporary fixing film.
[0207] In the method of peeling by heating the temporary fixing film to foam (or expand), the heating conditions are generally 100 to 250°C for 1 to 90 seconds or 5 to 15 minutes. In the method of peeling by irradiating the temporary fixing film from the substrate side to reduce the adhesive force of the temporary fixing film, the irradiation dose of ultraviolet light is generally 10 mJ / cm 2 ~1000mJ / cm 2 .
[0208] -Process (5)- The material forming the rewiring forming layer (insulating layer) is not particularly limited as long as it has insulating properties when the rewiring forming layer (insulating layer) is formed. From the viewpoint of the ease of manufacturing of the semiconductor chip package, it is preferably a photosensitive resin or a thermosetting resin. The resin combination of the present invention can also be well used for the formation of the rewiring forming layer.
[0209] After forming the rewiring formation layer, through holes can be formed in the rewiring formation layer to connect the semiconductor chip to the conductor layer described later. The through holes can be formed by a known method depending on the material of the rewiring formation layer.
[0210] -Process (6)- The material of the conductor layer formed on the rewiring forming layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer can be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above metals (for example, a nickel-chromium alloy, a copper-nickel alloy and a copper-titanium alloy) can be mentioned. Among them, from the viewpoints of versatility, cost, ease of pattern formation, etc. of the formation of the conductor layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy or copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is more preferred.
[0211] The conductor layer may have a single-layer structure or a multilayer structure in which two or more single metal layers or alloy layers composed of different types of metals or alloys are stacked. In the case of a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc, or titanium, or an alloy layer of a nickel-chromium alloy.
[0212] The thickness of the conductor layer varies depending on the desired design of the semiconductor chip package, but is generally 1 μm to 35 μm, preferably 1 μm to 20 μm.
[0213] In one embodiment, the conductor layer can be formed by plating. For example, the surface of the rewiring forming layer can be plated using conventionally known techniques such as a semi-additive process or a fully additive process to form a conductor layer having a desired wiring pattern. From the perspective of ease of production, formation using a semi-additive process is preferred. An example of forming a conductor layer using a semi-additive process is described below.
[0214] First, a plating seed layer is formed on the surface of the rewiring formation layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. The unnecessary plating seed layer is then removed by etching or the like, thereby forming a conductor layer (rewiring layer) having the desired wiring pattern.
[0215] It should be noted that the steps (5) and (6) may be repeated to alternately stack (stack) the conductor layer (rewiring layer) and the rewiring forming layer (insulating layer).
[0216] When manufacturing a semiconductor chip package, further steps may be performed, such as (7) forming a solder resist layer on a conductor layer (rewiring layer), (8) forming bumps, and (9) singulating a plurality of semiconductor chip packages into individual semiconductor chip packages. These steps may be performed using various methods known to those skilled in the art for use in manufacturing semiconductor chip packages.
[0217] The above-mentioned embodiment B is a method of first placing a semiconductor chip and forming a redistribution layer on the electrode pad surface, that is, chip-first mounting. st In addition to the chip-first method described above, the semiconductor chip package of the present invention can also utilize the redistribution layer first (RDL-1 st ) method, the redistribution layer is first installed (RDL-1 st ) method is to first set up a rewiring layer, and then set the semiconductor chip on the rewiring layer in a state where the electrode pad surface can be electrically connected to the rewiring layer and then seal it. st The construction method is still RDL-1 st The resin composition of the present invention can realize semiconductor chip packaging with extremely low transmission loss required for next-generation high-speed communication applications.
[0218] By using the resin composition of the present invention having a low dielectric loss tangent, good elongation, and excellent uniformity to form a cured product, a sealing layer, a redistribution formation layer, etc., regardless of whether the semiconductor package is a fan-in (Fan-In) type package or a fan-out (Fan-Out) type package, a semiconductor chip package with very little transmission loss can be achieved. In one embodiment, the semiconductor chip package of the present invention is a fan-out (Fan-Out) type package. The resin composition of the present invention is applicable to both fan-out panel level package (FOPLP) and fan-out wafer level package (FOWLP). In one embodiment, the semiconductor package of the present invention is a fan-out panel level package (FOPLP). In another embodiment, the semiconductor package of the present invention is a fan-out wafer level package (FOWLP).
[0219] [Printed wiring board] The resin composition of the present invention can be used to produce a printed wiring board. The present invention also provides such a printed wiring board. The printed wiring board of the present invention is characterized by comprising an insulating layer formed from a cured product of the resin composition of the present invention.
[0220] A printed wiring board can be produced, for example, by using the above-mentioned resin sheet through a method including the following steps (I) and (II): (I) laminating a resin sheet on an inner substrate so that the resin composition layer of the resin sheet is bonded to the inner substrate; and (II) curing (eg, thermally curing) the resin composition layer to form an insulating layer.
[0221] The "inner substrate" used in step (I) refers to a component that becomes a substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of a substrate is sometimes referred to as an "inner circuit substrate". In addition, an intermediate product that further forms an insulating layer and / or a conductor layer when manufacturing a printed wiring board is also included in the "inner substrate" referred to in the present invention. In the case where the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components can be used.
[0222] The inner substrate and the resin sheet can be laminated, for example, by heat-pressing the resin sheet onto the inner substrate from the support body side. As a component for heat-pressing the resin sheet onto the inner substrate (hereinafter also referred to as a "heat-pressing component"), for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) can be cited. It should be noted that the heat-pressing component can be directly pressed onto the resin sheet, or it can be pressed with an elastic material such as heat-resistant rubber so that the resin sheet fully conforms to the surface unevenness of the inner substrate.
[0223] The inner layer substrate and the resin sheet can be laminated by vacuum lamination. In vacuum lamination, the heating and pressing temperature is preferably in the range of 60°C to 160°C, more preferably 80°C to 140°C, the heating and pressing pressure is preferably in the range of 0.098 MPa to 1.77 MPa, more preferably 0.29 MPa to 1.47 MPa, and the heating and pressing time is preferably in the range of 20 seconds to 400 seconds, more preferably 30 seconds to 300 seconds. Lamination is preferably carried out under reduced pressure conditions of 26.7 hPa or less.
[0224] Lamination can be performed using a commercially available vacuum laminator. Examples of commercially available vacuum laminators include a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., and a batch vacuum pressure laminator.
[0225] After lamination, the laminated resin sheet can be smoothed by, for example, pressing a heat-pressing member from the support side under normal pressure (atmospheric pressure). The pressing conditions for the smoothing treatment can be the same as the heat-pressing conditions for the above-mentioned lamination. The smoothing treatment can be carried out by a commercially available laminating machine. It should be noted that the lamination and smoothing treatment can be carried out continuously using the above-mentioned commercially available vacuum laminating machine.
[0226] The support may be removed between steps (I) and (II) or after step (II). It should be noted that when a metal foil is used as the support, the conductive layer can be formed using the metal foil without peeling the support. Furthermore, when a metal foil with a supporting substrate is used as the support, the supporting substrate (and the peeling layer) can be peeled off. Thus, the conductive layer can be formed using the metal foil.
[0227] In step (II), the resin composition layer is cured (e.g., thermally cured) to form an insulating layer composed of a cured product of the resin composition. The curing conditions for the resin composition layer are not particularly limited, and conditions commonly used for forming an insulating layer of a printed wiring board can be used.
[0228] For example, the thermal curing conditions of the resin composition layer vary depending on the type of resin composition, etc. In one embodiment, the curing temperature is preferably 120° C. to 250° C., more preferably 150° C. to 240° C., and further preferably 180° C. to 230° C. The curing time is preferably 5 minutes to 240 minutes, more preferably 10 minutes to 150 minutes, and further more preferably 15 minutes to 120 minutes.
[0229] Before heat-curing the resin composition layer, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, before heat-curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50°C to 120°C, preferably 60°C to 115°C, and more preferably 70°C to 110°C for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0230] When manufacturing a printed wiring board, the process of (III) opening a hole in the insulating layer, the process of (IV) roughening the insulating layer, and the process of (V) forming a conductor layer can be further implemented. These processes (III) to (V) can be implemented according to various methods known to those skilled in the art used in the manufacture of the printed wiring board. It should be noted that when the support body is removed after process (II), the removal of the support body can be implemented between process (II) and process (III), between process (III) and process (IV), or between process (IV) and process (V). In addition, the formation of the insulating layer and the conductor layer of process (I) to process (V) can be repeatedly implemented as needed to form a multilayer wiring board.
[0231] In another embodiment, a printed wiring board can be produced using the above-mentioned prepreg. The production method is basically the same as when using a resin sheet.
[0232] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as through-holes and vias in the insulating layer. Step (III) can be carried out using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the holes can be appropriately determined based on the design of the printed wiring board.
[0233] Step (IV) is a step of roughening the insulating layer. Typically, contamination removal (decontamination) is also performed in step (IV). The steps and conditions for the roughening treatment are not particularly limited, and known steps and conditions commonly used in forming the insulating layer of a printed wiring board can be employed. For example, the insulating layer can be roughened by sequentially performing a swelling treatment using a swelling solution, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing solution.
[0234] The swelling liquid used in the roughening treatment is not particularly limited, and examples thereof include alkaline solutions, surfactant solutions, etc., preferably alkaline solutions, and more preferably sodium hydroxide solutions and potassium hydroxide solutions. Commercially available swelling liquids include, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan Co., Ltd. The swelling treatment using the swelling liquid is not particularly limited, and for example, the insulating layer can be immersed in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of controlling the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.
[0235] The oxidizing agent used in the roughening treatment is not particularly limited, and examples thereof include alkaline permanganate solutions obtained by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. As commercially available oxidizing agents, examples thereof include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosingsolution Securiganth P" manufactured by Atotech Japan Co., Ltd.
[0236] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and commercially available products include, for example, "Reduction solution Securiganth P" manufactured by Atotech Japan Ltd.
[0237] Treatment with a neutralizing solution can be performed by immersing the surface roughened with an oxidizing agent in a neutralizing solution at a temperature of 30° C. to 80° C. for 5 to 30 minutes. From the perspective of operability, a method in which the surface roughened with an oxidizing agent is immersed in a neutralizing solution at a temperature of 40° C. to 70° C. for 5 to 20 minutes is preferred.
[0238] Step (V) is a step of forming a conductive layer, and the conductive layer is formed on the insulating layer. Step (V) can be carried out in the same manner as step (6) described in relation to the method for manufacturing a semiconductor chip package.
[0239] The thickness of the conductor layer varies depending on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, preferably 5 μm to 30 μm.
[0240] The conductor layer can also be formed using metal foil. When using metal foil to form the conductor layer, process (V) is preferably implemented between process (I) and process (II). For example, after process (I), the support is removed and a metal foil is laminated on the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil can be implemented by a vacuum lamination method. The lamination conditions can be the same as those described for process (I). Then, process (II) is implemented to form an insulating layer. Then, the metal foil on the insulating layer can be utilized to form a conductor layer with a desired wiring pattern by conventionally known techniques such as a subtractive method and a modified semi-additive method.
[0241] Metal foil can be produced by known methods such as electrolysis and rolling. Commercially available metal foils include HLP foil and JXUT-III foil manufactured by JX Metals Co., Ltd., and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0242] Alternatively, as described above, when a metal foil or a metal foil with a supporting substrate is used as the support of the resin sheet, the conductor layer can be formed using the metal foil.
[0243] [Semiconductor devices] The semiconductor device of the present invention includes a layer formed from a cured product of the resin composition of the present invention. The semiconductor device of the present invention can be produced using the semiconductor chip package or printed wiring board of the present invention.
[0244] Examples of semiconductor devices include various semiconductor devices used in electrical products (such as computers, mobile phones, digital cameras, and televisions) and vehicles (such as motorcycles, automobiles, trains, ships, and aircraft). Example
[0245] The present invention will be described in detail below by way of examples. The present invention is not limited to these examples. It should be noted that, unless otherwise indicated, "parts" indicating an amount are "parts by mass."
[0246] <Synthesis Example 1: Synthesis of Resin X1> In a reaction vessel, 112 g of difunctional hydroxyl-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl equivalent = 1800 g / eq.), 272 g of anisole as a solvent, and 14 g of isophorone diisocyanate (IPDI) were added, and the temperature was raised to 50°C, and the reaction was carried out for about 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends ("SA90-100" manufactured by SABIC Innovative Plastics, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenone tetracarboxylic dianhydride (BTDA) were added to the reactants, and the temperature was raised to 140°C while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was considered the end point of the reaction, and the reaction mixture was cooled to room temperature. The reaction mixture was then filtered through a 100-mesh filter cloth to obtain resin X1 having an oligophenylene ether skeleton (non-volatile content 50% by mass, viscosity 6.0 Pa·s at 25°C, weight-average molecular weight 280,000, and glass transition temperature 0°C).
[0247] <Synthesis Example 2: Synthesis of Resin X2> In a reaction vessel, 60 g of difunctional hydroxyl-terminated polybutadiene ("G-1000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 1400, hydroxyl equivalent = 800 g / eq.), 220 g of anisole as a solvent, and 14 g of isophorone diisocyanate (IPDI) were added, and the temperature was raised to 50°C, and the reaction was carried out for about 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends ("SA90-100" manufactured by SABIC Innovative Plastics, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenone tetracarboxylic dianhydride (BTDA) were added to the reactants, and the temperature was raised to 140°C while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was considered the end point of the reaction, and the reaction mixture was cooled to room temperature. The reaction mixture was then filtered through a 100-mesh filter cloth to obtain Resin X2 having an oligophenylene ether skeleton (non-volatile content 50% by mass, viscosity 2.0 Pa·s at 25°C, weight-average molecular weight 260,000, glass transition temperature 0°C).
[0248] <Synthesis Example 3: Synthesis of Resin X3> Into a reaction vessel, 83 g of polycarbonate diol ("C-2015N" manufactured by Kuraray Co., Ltd., number average molecular weight = 2000, hydroxyl equivalent = 1000 g / eq.), 240 g of anisole as a solvent, and 14 g of isophorone diisocyanate (IPDI) were added, and the temperature was raised to 50°C, and the reaction was carried out for about 1 hour. Next, 145 g of oligophenylene ether resin containing phenolic hydroxyl groups at both ends ("SA90-100" manufactured by SABIC Innovative Plastics, hydroxyl equivalent = 800 g / eq.) and 1 g of benzophenone tetracarboxylic dianhydride (BTDA) were added to the reactants, and the temperature was raised to 140°C while stirring, and the reaction was carried out for about 4 hours. FT-IR was performed at 2250 cm -1 The disappearance of the NCO peak was confirmed. The disappearance of the NCO peak was considered the end point of the reaction, and the reaction mixture was cooled to room temperature. The reaction mixture was then filtered through a 100-mesh filter cloth to obtain Resin X3 having an oligophenylene ether skeleton (non-volatile content 50% by mass, viscosity 4.0 Pa·s at 25°C, weight-average molecular weight 254,000, glass transition temperature -4°C).
[0249] [Examples 1 to 9, Comparative Examples 1 to 3] (1) Preparation of resin composition Each component was weighed according to the formulation described in Table 1, and 15 parts of MEK was further mixed and uniformly dispersed using a high-speed rotary mixer to obtain a resin composition (resin varnish).
[0250] (2) Manufacturing of resin sheets A polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) with a release layer was prepared as a support. The obtained resin varnish was evenly applied onto the release layer of the support so that the thickness of the resin composition layer after drying was 50 μm. The resin composition was then dried at 80°C to 120°C (average 100°C) for 4 minutes to obtain a resin sheet having a layered structure of resin composition layer / support.
[0251] <Evaluation of elongation> The resin sheets obtained in the Examples and Comparative Examples were heated at 200°C for 90 minutes to thermally cure the resin composition layer. The support was then peeled off to obtain a cured product of the resin composition layer. This cured product was subjected to a tensile test using a Tensilon universal testing machine ("RTC-1250A" manufactured by Orientec Co., Ltd.) in accordance with Japanese Industrial Standards (JIS K7127). The elongation at break (%) at 23°C was measured and evaluated according to the following criteria. ×: Elongation at break is less than 0.9% △: Elongation at break is 0.9% or more and less than 1.2% ○: Elongation at break is 1.2% or more.
[0252] Uneven evaluation The resin sheets obtained in Examples and Comparative Examples were visually observed to confirm the presence or absence of surface unevenness, and were evaluated based on the following criteria. ○: No unevenness, uniform surface ×: There is unevenness.
[0253] <Measurement of Dielectric Loss Tangent> The resin sheets obtained in the examples and comparative examples were heated at 200°C for 90 minutes to thermally cure the resin composition layer. Next, the support was peeled off to obtain a cured product of the resin composition layer. The cured product was cut into 80 mm long and 2 mm wide test pieces for evaluation. For each test piece for evaluation, the dielectric loss tangent (Df value) was measured using the "HP8362B" manufactured by Agilent Technologies, Inc. using a resonant cavity perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C. Three test pieces were measured and their average value was calculated. The obtained average value was evaluated according to the following criteria. Evaluation Benchmarks ×: Dielectric loss tangent is 0.005 or more △: Dielectric loss tangent is higher than 0.004 and lower than 0.005 ○: Dielectric loss tangent is 0.004 or less.
[0254] Table 1 shows the results of Examples 1 to 9 and Comparative Examples 1 to 3.
[0255] [Table 1]
[0256] The details of the components listed in Table 1 are as follows: <Thermosetting resin> 828EL: Bisphenol A epoxy resin, functional group equivalent weight approximately 180 g / eq, manufactured by Mitsubishi Chemical Corporation HP-6000L: Naphthyl ether epoxy resin, functional group equivalent weight approximately 213 g / eq, manufactured by DIC Corporation YX4000H: Biphenyl-type epoxy resin, functional group equivalent weight 190 g / eq, manufactured by Mitsubishi Chemical Corporation. Curing agent KA-1160: Phenolic curing agent, cresol novolac resin, functional group equivalent weight 117g / eq, manufactured by DIC Corporation HPC-8000-65T: Active ester curing agent, functional group equivalent weight 223 g / eq, toluene solution with a non-volatile content of 65% by mass, manufactured by DIC Corporation V-03: Carbodiimide curing agent, functional group equivalent weight 216 g / eq, toluene solution with a non-volatile content of 50% by mass, manufactured by Nisshinbo Chemical Co., Ltd. Resin X Resins X1 to X3: Resins X1 to X3 synthesized in Synthesis Examples 1 to 3, toluene solutions containing 65% by mass of nonvolatile components <Resin Y> SA90: A resin containing an oligophenylene ether skeleton, with a weight-average molecular weight of 4400, manufactured by SABIC Innovative Plastics. SA9000: A resin containing an oligophenylene ether skeleton, with a weight-average molecular weight of 3900, manufactured by SABIC Innovative Plastics. OPE-2St-1200: A resin containing an oligophenylene ether skeleton, weight average molecular weight 3000, a toluene solution containing 65% nonvolatile matter, manufactured by Mitsubishi Gas Chemical Co., Ltd. X-12-1288C: Resin containing an oligophenylene ether skeleton, weight average molecular weight 3600, toluene solution containing 20% by mass of nonvolatile matter, manufactured by Shin-Etsu Chemical Co., Ltd. X-12-1288D: oligophenylene ether skeleton resin, weight average molecular weight 3500, toluene solution containing 20% by mass of non-volatile matter, manufactured by Shin-Etsu Chemical Co., Ltd. Curing accelerator 2P4MZ: Imidazole derivative, manufactured by Shikoku Chemicals Co., Ltd. ·DMAP: 4-dimethylaminopyridine <Free radical polymerization initiator> Dicumyl peroxide: Mitsui Fine Chemicals, Inc. (thermoplastic resin) YX7553BH30: phenoxy resin, a 1:1 mixed solution of MEK solution and cyclohexanone containing 30% by mass of non-volatile matter, manufactured by Mitsubishi Chemical Corporation <Inorganic fillers> SO-C2: Spherical silica surface-treated with an amino-based silane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, specific surface area 5.8 m 2 / g, made by Yadoma Co., Ltd.
Claims
1. A resin composition, wherein Comprising: an inorganic filler, a resin X containing a low polyphenylene ether backbone with a weight-average molecular weight Mw of MC, and a resin Y containing a low polyphenylene ether backbone with a weight-average molecular weight Mw of MD, where MC and MD satisfy the following Condition 1: <Condition 1> <1000000> MC > 5MD > 500.
2. A resin composition, wherein Comprising: an inorganic filler, a resin X containing a low polyphenylene ether backbone with a glass transition temperature of 25°C or lower, and a resin Y containing a low polyphenylene ether backbone different from resin X.
3. The resin composition according to claim 1 or 2, wherein When the resin components in the resin composition are set to 100% by mass, the total content of resin X and resin Y is 20% by mass or more and less than 70% by mass.
4. The resin composition according to claim 1, wherein When the non-volatile components in the resin composition are set to 100% by mass, the content of the inorganic filler is 50% by mass or more.
5. The resin composition according to claim 1 or 2, wherein Resin X contains one or more structural units selected from polyolefin structural units, polycarbonate structural units, polyether structural units, polyester structural units, poly(meth)acrylic structural units, and polysiloxane structural units.
6. The resin composition according to claim 1 or 2, wherein Further comprising a thermosetting resin.
7. The resin composition according to claim 1 or 2, which is used for sealing a semiconductor.
8. The resin composition according to claim 1 or 2, which is used for an insulating layer of a circuit board.
9. A cured product of the resin composition according to claim 1 or 2.
10. A resin sheet, wherein: Comprising a support and a layer of the resin composition according to claim 1 or 2 provided on the support. The resin sheet according to claim 10 , wherein The support is a thermoplastic resin film or a metal foil.
12. A semiconductor chip package, wherein: Comprising a sealing layer formed from the cured product of the resin composition according to claim 1 or 2.
13. A circuit substrate, wherein: Comprising an insulating layer formed from the cured product of the resin composition according to claim 1 or 2.
14. A semiconductor device, wherein: Comprising the semiconductor chip package according to claim 12.
15. A semiconductor device, wherein: Comprising the circuit board according to claim 13.
Citation Information
Patent Citations
Resin composition, and resin film with carrier, resin substrate, prepreg, metal-clad laminate, printed wiring board, and semiconductor device using the same
JP2022039594A
